Method of providing low gloss coating
Through the treatment technology of water-based radiation-curable polyurethane-vinyl polymer hybrid dispersion, the problem of degradation of coating performance caused by matting agents is solved, and the efficient production of low-gloss coatings is achieved, and the stain resistance and stability of the coating are improved.
Patent Information
- Application Number
- CN202380061143.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-24
- Filing Date
- 2023-08-22
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art requires the use of matting agents when creating low-gloss coatings, resulting in deterioration of the surface properties of the coating, reducing stain resistance, and matting agents easily migrate to the surface of the coating, affecting the stability of gloss.
Low gloss coating was obtained by using aqueous radiation-curable polyurethane-vinyl polymer mixed dispersion, and pretreated with ultraviolet light with wavelength ≤220 nm under an inert atmosphere, and then curing with ultraviolet light or electron beam with wavelength ≥300 nm.
It is achieved to obtain a low-gloss coating without using matting agent, which improves the stain resistance and gloss stability of the coating, while avoiding potential safety hazards brought by matting agents.
Smart Images

Figure BDA0005279698410000291 
Figure BDA0005279698410000301 
Figure BDA0005279698410000331
Abstract
Description
[0001] The present invention relates to the field of waterborne radiation-curable polyurethane-vinyl polymer hybrid coating compositions having low gloss. The present invention also relates to a process for producing low gloss coatings from waterborne radiation-curable coating compositions.
[0002] Aqueous radiation-curable polyurethane-vinyl polymer hybrid dispersions are widely used in the production of materials such as coatings, inks and / or adhesives. After applying the aqueous radiation-curable polyurethane-vinyl polymer hybrid dispersion on a substrate, the dispersion is dried to obtain an at least partially dried coating composition, and then the at least partially dried coating composition is irradiated with ultraviolet light of a wavelength ≥ 300 nm or with an electron beam to obtain a radiation-cured coating. Such radiation-cured coatings exhibit very good properties on many substrates such as wood, plastics, concrete, metals, glass and / or textiles. The structure and functionality of the radiation-curable polyurethane-vinyl polymer hybrid coating composition are known to control factors such as curing speed, degree of crosslinking and the final properties of the coating (especially properties such as flexibility, hardness, adhesion, scratch resistance and / or chemical resistance).
[0003] "Low gloss" surfaces give products a highly sought-after aesthetic effect, especially in the wooden furniture, flooring and wall covering industries, as they can create a very natural look, which helps to emphasize the materiality of the article even more. Currently, the creation of matt surfaces usually involves the use of coating products whose formulations contain matting agents made of organic and / or inorganic substances, which, by positioning themselves on the coating surface and / or appearing on the coating surface, are able to act on the degree of reflection of light to give the observer the visual perception of a low gloss surface. However, the use of matting agents leads to a deterioration of the surface properties of the coating, as they do not participate in the crosslinking and polymerization processes so that the stain resistance is significantly reduced. In addition, matting agents tend to migrate to the coating surface after application, so that the matting agents may be lost upon mechanical deformation, such as caused by scratching, so that the gloss increases.
[0004] The use of matting agents also seriously reduces the tolerance to typical household chemicals such as coffee, red wine and mustard. The long-term effect of these household chemicals at least leads to a reduction in the quality of the coating and may even lead to its complete destruction. Silicon dioxide-based compounds are the main matting agents used. Usually, silicon dioxide-based matting agents are porous, as shown by their oil absorption values of 100-500 ml / 100 g. The disadvantage of using this type of matting agent in coating formulations is that it not only deteriorates the quality of the final coating, but also leads to undesirable coloring of the exposed coating area, because especially colored household stains such as coffee, red wine and mustard (part of DIN 1B) are easily absorbed by porous silica, and because these stains contain organic dyes, this can lead to undesirable coloring of the exposed coating area.
[0005] The object of the present invention is to provide a process for obtaining low-gloss coatings from aqueous radiation-curable polyurethane-vinyl polymer hybrid dispersions without having to use matting agents.
[0006] According to the present invention, there is provided a method for producing a coating from an aqueous radiation-curable coating composition, wherein the method comprises the following steps in order (1) to (4):
[0007] (1) applying an aqueous radiation-curable coating composition onto a surface of a substrate,
[0008] (2) drying the aqueous radiation-curable coating composition to provide an at least partially dried coating composition,
[0009] (3) irradiating the at least partially dried coating composition with ultraviolet light having a wavelength of ≤220 nm under an inert atmosphere, and then
[0010] (4) Irradiation with ultraviolet light with a wavelength of ≥300 nm or electron beam,
[0011] The aqueous radiation-curable coating composition is a dispersion comprising:
[0012] (A) at least one blend (A) of at least one polyurethane and at least one vinyl polymer, wherein
[0013] The hybrid (A) is obtained by free radical polymerization of at least one vinyl monomer in the presence of at least one water-dispersible polyurethane,
[0014] The hybrid (A) contains substantially no radiation-curable ethylenically unsaturated bonds,
[0015] The polyurethane of the hybrid (A) has a urea group (—NH—CO—NH—) concentration of at least 0.1 milliequivalent / gram of polyurethane and at most 1.9 milliequivalent / gram of polyurethane, and
[0016] The weight ratio of the polyurethane and the vinyl polymer of the blend (A) is 25:75 to 95:5;
[0017] (B) at least one radiation-curable diluent (B) having a molar mass of less than 750 g / mol and having an acrylate functionality of 2 to 5, and
[0018] (C) water and optionally an organic solvent, whereby the optional organic solvent is present in an amount of up to 30 wt.-% (percent by weight), based on the total amount of water and organic solvent,
[0019] The amount of (A) is 30 to 85% by weight, and the amount of (B) is 15 to 70% by weight, based on the total amount of (A) and (B).
[0020] It has surprisingly been found that the process of the present invention, which comprises pre-treating the coating composition with ultraviolet light having a wavelength of ≤ 220 nm (also further referred to as an excimer irradiation step), enables obtaining low gloss coatings from aqueous radiation-curable polyurethane-vinyl polymer hybrid dispersions as defined herein, without the use of matting agents, while the aqueous dispersible polyurethane-vinyl polymer hybrid is substantially free of radiation-curable ethylenically unsaturated bonds. More particularly, with the process of the present invention, coatings having a gloss measured at 20° angular geometry of less than 10 gloss units, and preferably a gloss measured at 60° angular geometry of less than 40 gloss units (further referred to as low gloss), more preferably a gloss measured at 60° angular geometry of less than 30 gloss units, more preferably less than 20 gloss units, even more preferably less than 10 gloss units, and even more preferably less than 5 gloss units can be obtained. The aqueous radiation-curable coating composition according to the invention allows to obtain a difference in gloss measured at 60° angular geometry with and without an excimer irradiation step of at least 40 gloss units, preferably at least 50 gloss units, more preferably at least 60 gloss units. It has also been surprisingly found that the process of the invention allows to obtain a low-gloss coating from an aqueous radiation-curable polyurethane-vinyl polymer hybrid dispersion as defined herein without the use of a matting agent, while improving the coffee, red wine and / or mustard resistance of the coating compared to when the dispersion contains a matting agent. It has also been surprisingly found that the process of the invention allows to obtain a low-gloss coating from an aqueous radiation-curable polyurethane-vinyl polymer hybrid dispersion as defined herein without the use of a matting agent, while improving the coffee, red wine and / or mustard resistance of the coating compared to a coating obtained without the excimer irradiation step, while the aqueous dispersible polyurethane-vinyl polymer hybrid is substantially free of radiation-curable ethylenically unsaturated bonds.
[0021] Another advantage of the present invention is that no matting agents need to be handled, which is advantageous because matting agents have a large surface area and contain a large proportion of small dust-forming particles that may pose an exposure and explosion hazard. Another advantage of not having to use matting agents to obtain low-gloss coatings is that coating compositions with less or no sedimentation and thus improved storage stability can be achieved. Another advantage of the process of the present invention is that coatings with significantly higher smoothness can be obtained than when the coating contains matting particles.
[0022] WO-A-2013 / 092521 describes a method for producing uniform matte coatings on flat surfaces based on so-called 100% radiation-curable coating compositions. In this method, first, a 100% radiation-curable coating composition containing a low molecular weight radiation-curable oligomer as a binder and optionally one or more reactive diluents to reduce the viscosity is applied to the surface of a flat substrate using a spiral scraper. This wet paint layer is then irradiated with a wavelength of 200 to 420 nm and a radiation dose of 25 to 120 mJ / cm 2 The coating composition is then irradiated with ultraviolet light to cause partial gelation of the coating composition. The coating thus obtained is then irradiated with ultraviolet light from an excimer lamp having a wavelength of 120nm to 230nm under an inert gas, and then a conventional UV emitter is used for final curing. A 100% radiation-curable coating composition refers to a coating composition having a solid content of 100% by weight. A 100% radiation-curable coating composition refers to a homogeneous system having only one phase, while an aqueous radiation-curable polyurethane-vinyl polymer hybrid coating composition as defined herein is a dispersion having at least two phases, wherein one phase contains discrete particles (colloidally dispersed particles) distributed throughout an aqueous medium, the particles being a dispersed phase, and the aqueous medium being a continuous phase. WO-A-2013 / 092521 does not teach that a low gloss coating can be obtained by an aqueous coating composition, let alone by an aqueous radiation-curable polyurethane-vinyl polymer hybrid dispersion as defined herein, and does not mention the stain resistance of the cured coating.
[0023] Another disadvantage of the method described in WO-A-2013 / 092521 is that the viscosity of the 100% radiation-curable coating composition is generally high, so that some application techniques, such as spraying, are difficult or impossible to use to apply the coating composition to the substrate. Spraying application can be advantageously used to apply the coating composition to substrates with more complex shapes, such as furniture or decorative frames. The viscosity of the 100% radiation-curable coating composition can be reduced by adding a monofunctional diluent with a low molecular weight, so that a viscosity that allows the radiation-curable coating composition to be deposited on the substrate by spraying can be obtained. However, applying a 100% radiation-curable coating composition by spraying inherently results in a coating having a high coating thickness.
[0024] Another advantage of using an aqueous radiation-curable polyurethane-vinyl polymer hybrid dispersion as defined herein is that the viscosity can be controlled by adjusting the solids content with water, so that the coating can be easily applied by spraying using the process of the present invention even at low coating thicknesses (e.g. a wet coating thickness of 25 microns).
[0025] Another advantage of the fact that aqueous radiation curable polyurethane-vinyl polymer hybrid dispersions as defined herein are easier to apply by spraying is that the process of the invention also enables low gloss coatings to be obtained on articles of more complex shapes, such as decorative frames, with a more uniform gloss of the coated article.
[0026] Another advantage of using an aqueous radiation curable coating composition as defined herein is that low gloss can be imparted to coatings having relatively low thicknesses (e.g., coating thicknesses of 50 microns or even less) using the process of the present invention. Another advantage of the present invention is that the gloss of the coating can be adjusted with the residual water and / or organic solvent content present in the at least partially dried coating composition.
[0027] Furthermore, it has surprisingly been found that with the coating composition as claimed, low gloss coatings can be obtained in only 2 irradiation steps (i.e. steps (3) and (4)), in particular for coatings with a wet thickness (before drying) of at most 300 microns, or at most 250 microns, or at most 200 microns or at most 175 microns, in particular at most 150 microns, more in particular at most 125 microns, more in particular at most 100 microns, and more in particular at most 75 microns. WO-A-2013 / 092521 teaches that an additional partial gelling irradiation step is required before the excimer irradiation step (step (3) of the method of the invention) and the final curing step (step (4) of the method of the invention), and thus WO-A-2013 / 092521 teaches that three irradiation steps are required to obtain a low gloss / matt coating with a homogeneous surface structure, see in particular Table 2.
[0028] The aqueous radiation curable coating composition used in the process of the present invention comprises the polyurethane-vinyl polymer hybrid in dispersed form, ie the composition comprises dispersed particles of the polyurethane-vinyl polymer hybrid.
[0029] A dispersion refers to a system having at least two phases, one of which contains discrete particles (colloidally dispersed particles) distributed throughout a bulk substance, the particles being the dispersed phase, and the bulk substance being the continuous phase. The continuous phase of an aqueous dispersion is provided at least in part by water. Preferably, the continuous phase of the dispersion of the present invention comprises at least 75% by weight, more preferably at least 80% by weight, and even more preferably at least 90% by weight of water (relative to the continuous phase).
[0030] The aqueous coating composition used in the method of the present invention is radiation curable. Radiation curable means that radiation is required to initiate crosslinking of the dispersion. The aqueous coating composition used in the method of the present invention contains ethylenically unsaturated (C=C) bond functional groups, which can crosslink by free radical polymerization under the influence of irradiation in combination with the presence of a (photo)initiator.
[0031] As used herein, the acrylate functionality of a compound is the number of acrylate functional groups per molecule of the compound.
[0032] The acrylate functional group has the formula:
[0033] CH2=CH-C(O)O-
[0034] For all upper and / or lower limits of any range given herein, unless otherwise specifically stated, the boundary values are included in the given range. Thus, when reference is made to x to y, x and y and all intermediate values are included.
[0035] As used herein, the acid value of a polymer (e.g., the acid value of a polyurethane, a vinyl polymer, and a polyurethane-vinyl polymer hybrid (A)) is a theoretical acid value, determined according to the following formula:
[0036] AV polymer [mg KOH / g solid polymer] = (total number of acidic groups present in the polymer (in moles) / total weight of polymer)*56.1*1000.
[0037] Polyurethane-vinyl polymer blend (A)
[0038] The at least one hybrid (A) of at least one polyurethane and at least one vinyl polymer is obtained by free-radical polymerization of one or more vinyl monomers in the presence of at least one water-dispersible polyurethane as described below.
[0039] The radiation curable diluent (B) is added after free radical polymerization of the vinyl monomers to obtain the vinyl polymer of the polyurethane-vinyl polymer hybrid. The polyurethane is preferably prepared in the presence of at least a portion of the one or more vinyl monomers used to prepare the vinyl polymer.
[0040] The vinyl polymer is advantageously formed in situ by polymerizing one or more vinyl monomers in the presence of a preformed aqueous polyurethane dispersion.
[0041] A polyurethane-vinyl polymer hybrid refers to a vinyl polymer prepared by free radical polymerization of vinyl monomers in the presence of a polyurethane, by forming an aqueous dispersion of the polyurethane resin and polymerizing one or more vinyl monomers to form the vinyl polymer, such that the vinyl polymer is incorporated in situ into the aqueous dispersion by polymerizing the vinyl monomers used to form the vinyl polymer in the presence of the polyurethane resin. The vinyl monomers are added before, during and / or after the preparation of the polyurethane and polymerized by adding a free radical initiator to polymerize the vinyl monomers in the presence of the polyurethane.
[0042] The weight ratio of polyurethane to vinyl polymer in the polyurethane-vinyl polymer blend (A) is 25:75 to 95:5, preferably 30:70 to 90:10, more preferably 40:60 to 88:12, more preferably 50:50 to 85:15, more preferably 65:35 to 80:20.
[0043] The theoretical acid value of the polyurethane-vinyl polymer hybrid (A) is preferably in the range of 3 to 45 mg KOH / g of hybrid (A), preferably 4 to 40 mg KOH / g of hybrid (A), more preferably 5 to 35 mg KOH / g of hybrid (A), more preferably 6 to 28 mg KOH / g of hybrid (A).
[0044] Polyurethane
[0045] The polyurethane has a urea group (-NH-CO-NH-) concentration of at least 0.1 and at most 1.9 milliequivalents / gram of polyurethane. It has surprisingly been found that the use of a polyurethane having a urea bond concentration of more than 1.9 milliequivalents / gram of polyurethane in a process comprising steps (1) to (4) does not result in a low gloss coating. The polyurethane preferably has a urea group content of at most 1.7 milliequivalents (meq) / gram of polyurethane, more preferably at most 1.5 meq / g of polyurethane, even more preferably at most 1.3 meq / g (A), even more preferably at most 1.1 meq / g of polyurethane, even more preferably at most 0.9 meq / g of polyurethane, and preferably at least 0.2 meq / g of polyurethane, more preferably at least 0.3 meq / g of polyurethane, more preferably at least 0.35 meq / g of polyurethane, even more preferably at least 0.4 meq / g of polyurethane. The urea group (-NH-CO-NH-) concentration of the polyurethane is determined by calculation as further described herein.
[0046] Methods for preparing polyurethanes are known in the art and are described, for example, in G. Oertel, Polyurethane Handbook, 2nd edition, published by Carl Hanser, 1994. Typically, an isocyanate-terminated polyurethane prepolymer is first formed and then chain extended, preferably with a nitrogen-containing compound.
[0047] The polyurethane is preferably prepared by the reaction of at least the following components, and the polyurethane (A) is more preferably prepared by the reaction of the following components:
[0048] (A1) at least one polyisocyanate,
[0049] (A2) at least one isocyanate-reactive compound containing at least one salt group capable of rendering the polyurethane dispersible in water and / or a functional group convertible into a salt group capable of rendering the polyurethane dispersible in water, preferably an acid functional group,
[0050] (A3) optionally, at least one isocyanate-reactive compound containing at least one nonionic group capable of rendering the polyurethane dispersible in water,
[0051] (A4) at least one isocyanate-reactive polyol different from (A2) and (A3) having an OH number of 25 to 225 mg KOH / g solids,
[0052] (A5) optionally, at least one isocyanate-reactive polyol different from (A2) and (A3) having an OH value of more than 225 mg KOH / g solid and less than 1850 mg KOH / g solid, and
[0053] (A6) water and / or at least one nitrogen-containing chain extender compound.
[0054] Preferred isocyanate-reactive groups are hydroxyl groups.
[0055] Component (A1)
[0056] At least one polyisocyanate is used as component (A1). The at least one polyisocyanate used according to the present invention is preferably selected from diisocyanates having the general formula Y(NCO)2, wherein Y is a C4-12 divalent aliphatic hydrocarbon group, i.e. an aliphatic diisocyanate compound, a C6-15 divalent alicyclic hydrocarbon group, i.e. an alicyclic diisocyanate compound, a C6-15 divalent aromatic hydrocarbon group, i.e. an aromatic diisocyanate compound, or a C7-15 divalent araliphatic hydrocarbon group, i.e. an araliphatic diisocyanate compound.
[0057] Examples of suitable organic difunctional isocyanates (component (A1)) include ethylene diisocyanate, 1,5-pentamethylene diisocyanate (PDI), 1,6-hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), cyclohexane-1,4-diisocyanate, dicyclohexylmethane diisocyanate (HMDI), such as 4,4'-dicyclohexylmethane diisocyanate (4,4'-H 12 The preferred organic difunctional isocyanates are IPDI, HMDI and HDI. Mixtures of organic difunctional isocyanates may also be used.
[0058] Typically, the amount of component (A1) is 5 to 55% by weight, preferably 10 to 45% by weight, most preferably 15 to 40% by weight, based on the weight of the polyurethane.
[0059] Component (A2)
[0060] As component (A2) at least one isocyanate-reactive compound is used which contains at least one salt group, preferably an acidic group, which makes the polyurethane dispersible in water and / or at least one functional group, preferably an acidic group, which can be converted into a salt group, preferably an acidic group, which makes the polyurethane dispersible in water by reaction with a neutralizing agent.
[0061] Typically, the amount of component (A2) is 1 to 15 wt%, preferably 2 to 12 wt%, and even more preferably 3 to 10 wt%, based on the weight of the polyurethane.
[0062] According to the present invention, the acidic group is preferably selected from a carboxylic acid group, a sulfonic acid group and / or a phosphoric acid group. Component (A2) is preferably a compound having two or more hydroxyl groups and / or two or more amino groups. Preferably, at least one compound having two or more hydroxyl groups is used as component (A2). A combination of at least one compound containing a carboxylic acid group and at least one compound containing a sulfonic acid group can be used. Preferred components (A2) are dihydroxy alkanoic acids and diamine sulfonates.
[0063] Preferably, at least one compound containing carboxylic acid groups is used as component (A2).
[0064] In the case where component (A2) contains at least one functional group that can be converted into a salt group by reacting with a neutralizing agent, the neutralizing agent for deprotonating (neutralizing) the functional group (preferably a carboxylic acid group, a sulfonic acid group and / or a phosphoric acid group, more preferably a carboxylic acid group) is preferably selected from ammonia, (tertiary) amines, metal hydroxides and any mixture thereof. Suitable tertiary amines include triethylamine and N,N-dimethylethanolamine. Suitable metal hydroxides include alkali metal hydroxides, such as lithium hydroxide, sodium hydroxide and potassium hydroxide. Preferably, at least 30 mol%, more preferably at least 50 mol%, and most preferably at least 70 mol% of the total molar amount of the neutralizing agent are alkali metal hydroxides, preferably selected from lithium hydroxide, sodium hydroxide, potassium hydroxide and any mixture thereof. Preferably, the neutralizing agent for deprotonating (neutralizing) the carboxylic acid group, the sulfonic acid group and / or the phosphoric acid group is an alkali metal hydroxide. As used herein, the neutralizing agent (if any) is not regarded as a component from which the structural units of the polyurethane are derived. Therefore, the calculation of the weight of the polyurethane does not take into account the amount of the neutralizing agent (if any) used to prepare the polyurethane.
[0065] In one embodiment of the present invention, component (A2) comprises or consists essentially of or consists of at least one diamine sulfonate. In this embodiment, the isocyanate-terminated polyurethane prepolymer is generally first formed by reaction of components (A1) and (A4) and optionally (A3) and optionally (A5), and then further reacted with the diamine sulfonate (A2) and water and optionally a nitrogen-containing chain extender compound (A6). A preferred diamine sulfonate is the sodium salt of 2-[(2-aminoethyl)amino]ethanesulfonic acid.
[0066] In a preferred embodiment of the present invention, component (A2) comprises or consists essentially of or consists of at least one dihydroxyalkanoic acid. In this embodiment, the isocyanate-terminated polyurethane prepolymer is usually first formed by reaction of components (A1), (A2) and (A4) and optionally (A3) and optionally (A5), and then chain extended with water and / or nitrogen-containing chain extender compounds (A6).
[0067] Preferred dihydroxyalkanoic acid is α,α-dimethylolpropionic acid and / or α,α-dimethylolbutanoic acid. More preferably, the dihydroxyalkanoic acid is α,α-dimethylolpropionic acid.
[0068] The amount of acidic groups present in the polyurethane is preferably such that the theoretical acid value of the polyurethane is from 5 to 50, more preferably from 10 to 40, still more preferably from 15 to 30 mg KOH / g polyurethane solids.
[0069] Component (A3)
[0070] Optionally, at least one isocyanate-reactive compound containing at least one nonionic group which makes the polyurethane dispersible in water is used as component (A3).
[0071] The polyurethane can be further stabilized in dispersion by nonionic functional groups incorporated into the polyurethane. Thus, the polyurethane can be at least partially non-ionically stabilized by chemically incorporating nonionic groups into the polyurethane to provide at least a portion of the hydrophilicity required to enable the polyurethane to be stably dispersed in an aqueous dispersion medium. A preferred nonionic water-dispersing group is polyethylene oxide.
[0072] Preferred component (A3) is a polyethylene glycol having at least 5 ethylene oxide repeating units, preferably at least 10, more preferably at least 15 ethylene oxide repeating units, and preferably up to 120, more preferably up to 80, and even more preferably up to 40 ethylene oxide repeating units. More preferred component (A3) is a polyethylene glycol having 10 to 60, and preferably 15 to 30 ethylene oxide repeating units.
[0073] Non-limiting examples of suitable components (A3) include Ymer available from Perstorp TM N120 and MPEG 750.
[0074] In the case of using component (A3) to prepare polyurethane, the amount of component (A3) is generally 1 to 15% by weight, preferably 1 to 12% by weight, most preferably 1 to 5% by weight, based on the weight of the polyurethane.
[0075] Component (A4)
[0076] Use at least one OH value with 25 to 225mg KOH / g solid and be different from the isocyanate reactive compound of (A2) and (A3) as component (A4).Preferred component (A4) is the polyol that can be selected from any polyol chemical category that can be used for polyurethane synthesis.Especially, polyol can be polyester polyol, polyesteramide polyol, polyether polyol, polythioether polyol, polycarbonate polyol, polyacetal polyol, polyvinyl polyol and / or polysiloxane polyol.Preferably polyester polyol, polyether polyol and polycarbonate polyol.Preferably, the OH value of component (A4) is in the range of 35 to 190mg KOH / g solid, more preferably in the range of 45 to 125mg KOH / g solid.OH value is provided by supplier and can be measured by the titration of alcohol of known mass according to ASTM D4274, and is expressed as mg KOH / g.
[0077] Typically, the amount of component (A4) is from 20 to 80% by weight, preferably from 30 to 70% by weight, more preferably from 35 to 65% by weight, based on the weight of the polyurethane.
[0078] Component (A5)
[0079] Optionally, at least one isocyanate-reactive compound having an OH number of more than 225 mg KOH / g solid and less than 1850 mg KOH / g solid and different from (A2) and (A3) is used as component (A5).
[0080] Examples of suitable components (A5) include neopentyl glycol (NPG), cyclohexanedimethanol (CHDM), butanediol, hexanediol and trimethylolpropane.
[0081] In the case of using component (A5) to prepare polyurethane, the amount of component (A5) is generally 0.5 to 10% by weight, preferably 1 to 8% by weight, most preferably 2 to 6% by weight, based on the weight of the polyurethane.
[0082] Component (A6)
[0083] As chain extender component (A6) water and / or at least one nitrogen-containing chain extender compound are used.
[0084] For water chain extension, two NCO groups will form one urea bond. First, the NCO group reacts with water to form an unstable carbamic acid intermediate, which decomposes into CO2 and an amine group, which will then react with another NCO group to form a urea group. However, water chain extension is very slow compared to chain extension using nitrogen-containing chain extenders. Therefore, if a nitrogen-containing chain extender compound is applied, the calculation for the urea group concentration assumes that the isocyanate groups of the polyurethane prepolymer react first with the nitrogen-containing chain extender and during and / or after dispersion, the isocyanate groups still present on the polyurethane prepolymer react with water to form urea groups.
[0085] Examples of suitable nitrogen-containing chain extenders include amino alcohols, primary or secondary diamines or polyamines (including compounds containing primary and secondary amino groups), hydrazines and substituted hydrazines. Examples of such chain extender compounds useful herein include 2-(methylamino)ethylamine, aminoethylethanolamine, aminoethylpiperazine, diethylenetriamine and alkylenediamines such as ethylenediamine and 1,6-hexamethylenediamine, and cyclic amines such as isophoronediamine. The following compounds may also be useful: hydrazine, azines such as acetone azines, substituted hydrazines such as dimethylhydrazine, 1,6-hexamethylene-bishydrazines, carbon dihydrazides, hydrazides of dicarboxylic acids such as adipic acid dihydrazides, oxalic acid dihydrazides and isophthalic acid dihydrazides, hydrazides made by reacting lactones with hydrazides, bis-semi-carbazides and bis-hydrazide carbonates of diols. Water-soluble nitrogen-containing chain extenders are preferred.
[0086] Preferably, the nitrogen-containing chain extender compound is selected from the group consisting of amino alcohols, primary or secondary diamines, hydrazines, substituted hydrazines, substituted hydrazides, and any mixtures thereof.
[0087] When the chain extender is not water, such as hydrazine, it can be added to the aqueous dispersion of the isocyanate-terminated polyurethane prepolymer, or alternatively it can already be present in the aqueous medium when the isocyanate-terminated polyurethane prepolymer is dispersed in the aqueous medium. Chain extension can be carried out at a convenient temperature of about 5°C to 95°C, or more preferably about 10°C to 60°C.
[0088] If used, the total amount of nitrogen-containing chain extender compounds employed should be such that the ratio of active hydrogens in the chain extender to isocyanate groups in the polyurethane prepolymer is preferably 0.1:1 to 2:1, more preferably 0.6:1 to 1.4:1, and especially preferably 0.8 to 1.2.
[0089] Preferably, component (A6) is water or water and at least one NH x (where x is 1 or 2) functionality, more preferably having 2 NH xMore preferably, component (A6) comprises at least one NH containing chain extender having 2 or 3 NH x (where x is 1 or 2) functionality, more preferably having 2 NH x More preferably, component (A6) is water and at least one NH containing chain extender having 2 or 3 NH x (where x is 1 or 2) functionality, more preferably having 2 NH x The functional nitrogen-containing chain extender is preferably selected from diamines and / or dihydrazides.
[0090] Vinyl polymer
[0091] Vinyl polymers are obtained by polymerizing vinyl monomers using conventional free radical initiator systems. Suitable free radical initiators include mixtures that are distributed between an aqueous phase and an organic phase. Suitable free radical initiators include inorganic peroxides, such as ammonium persulfate, hydrogen peroxide, organic peroxides, such as benzoyl peroxide, alkyl hydroperoxides, such as tert-butyl hydroperoxide and cumene hydroperoxide; dialkyl peroxides, such as di-tert-butyl peroxide; peroxyesters, such as tert-butyl peroxybenzoate, etc.; mixtures can also be used. In some cases, it is advantageous to use peroxy compounds in combination with suitable reducing agents (redox systems) such as isoascorbic acid. Azo compounds, such as azobisisobutyronitrile, can also be used. Metal compounds such as Fe.EDTA (EDTA is ethylenediaminetetraacetic acid) can also be used as part of the redox initiator system. The amount of initiator or initiator system used is conventional, for example, in the range of 0.05 to 6% by weight based on the weight of the vinyl monomer used.
[0092] Preferably at least 80% by weight, more preferably at least 95% by weight, most preferably 100% by weight of the total weight of vinyl monomers used are α,β-monounsaturated vinyl monomers.
[0093] Examples of vinyl monomers include, but are not limited to, 1,3-butadiene, isoprene; trifluoroethyl (meth)acrylate (TFEMA); dimethylaminoethyl (meth)acrylate (DMAEMA); styrene, α-methylstyrene, (meth)acrylamide, and (meth)acrylonitrile; vinyl halides such as vinyl chloride; vinylidene halides such as vinylidene chloride; vinyl ethers; vinyl esters such as vinyl acetate, vinyl propionate, vinyl laurate; versatate vinyl esters such as VeoVa 9 and VeoVa 10 (VeoVa is a trademark of Resolution); heterocyclic vinyl compounds; alkyl esters of monoethylenically unsaturated dicarboxylic acids such as di-n-butyl maleate and di-n-butyl fumarate; dialkyl itaconates such as dimethyl itaconate, diethyl itaconate, dibutyl itaconate, and in particular esters of acrylic acid and methacrylic acid of the formula wherein R 4 is H or methyl, R 5 is an optionally substituted alkyl group of 1 to 20 carbon atoms (more preferably 1 to 8 carbon atoms) or a cycloalkyl group of 3 to 20 carbon atoms (more preferably 3 to 6 carbon atoms), examples of which are methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate (all isomers), octyl (meth)acrylate (all isomers), 2-ethylhexyl (meth)acrylate, isopropyl (meth)acrylate and n-propyl (meth)acrylate. Preferred formula CH2=CR 4 -COOR 5 Monomers of the invention include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate (all isomers), octyl (meth)acrylate (all isomers), ethylhexyl acrylate (all isomers), and isobornyl (meth)acrylate.
[0094] Vinyl monomers can include vinyl monomers with functional groups such as crosslinking agent groups and / or water dispersible groups. This functional group can be directly introduced into the vinyl polymer by free radical polymerization, or can be introduced into the functional group by the reaction of reactive vinyl monomers, which react with the reactive compounds with required functional groups subsequently. The example of suitable vinyl monomers providing crosslinking groups includes acrylic acid and methacrylic acid monomers with at least one free carboxyl or hydroxyl, epoxy, acetoacetoxy or carbonyl, such as acrylic acid and methacrylic acid, glycidyl acrylate, glycidyl methacrylate, acetoacetoxyethyl methacrylate, allyl methacrylate, tetraethylene glycol dimethacrylate, divinylbenzene and diacetone acrylamide.
[0095] Vinyl monomers providing ionic or potentially ionic water-dispersing groups that can be used as additional vinyl monomers include, but are not limited to, (meth)acrylic acid, itaconic acid, maleic acid, citraconic acid, and styrene sulfonic acid.
[0096] Vinyl monomers providing nonionic water dispersing groups may also be used, including alkoxy polyethylene glycol (meth) acrylates, preferably having a number average molecular weight of 140 to 3000. Examples of such monomers available commercially include ω-methoxy polyethylene glycol (meth) acrylates. The at least one vinyl polymer of the hybrid (A) preferably has a calculated glass transition temperature Tg of -55°C to 115°C, preferably -20°C to 115°C, more preferably -5°C to 115°C, more preferably 35°C to 115°C, more preferably 45°C to 115°C.
[0097] As used herein, the glass transition temperature is determined by calculation using the Fox equation. Thus, the T of a copolymer having "n" copolymerized comonomers is g (Kelvin) is the weight fraction W of each comonomer type and the T of the homopolymer derived from each comonomer. g (Kelvin) (e.g., as listed in J. Brandrup, EH Immergut, Polymer handbook 4th edition, page VI 193), is given by the following equation:
[0098] 1 / T g =Σ(W n / Tg n ).
[0099] The calculated T g (in Kelvin) can be easily converted to ° C. Preferably, at least 30% by weight, more preferably at least 50% by weight, and even more preferably at least 70% by weight of the total amount of vinyl monomers used to prepare the vinyl polymer are selected from methyl methacrylate, n-butyl acrylate, n-butyl methacrylate, 2-ethylhexyl acrylate, 2-octyl acrylate, styrene and mixtures of two or more of the monomers. Preferably, the vinyl monomers used to prepare the vinyl polymer are selected from styrene, methyl methacrylate, ethyl acrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, 2-octyl acrylate and mixtures thereof. More preferably, at least 30% by weight, preferably at least 50% by weight, and even more preferably at least 70% by weight of the total amount of vinyl monomers used to prepare the vinyl polymer are styrene, methyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, 2-octyl acrylate and mixtures thereof.
[0100] The theoretical acid value of the vinyl polymer of blend (A) is preferably 0 to 10 mg KOH / g vinyl polymer solid, more preferably less than 8 mg KOH / g vinyl polymer solid, more preferably less than 5 mg KOH / g vinyl polymer solid, more preferably less than 3 mg KOH / g vinyl polymer solid.
[0101] The polyurethane-vinyl polymer hybrid (A) present in the aqueous radiation-curable coating composition of the present invention is substantially free of radiation-curable ethylenically unsaturated bonds. As used herein, the polyurethane-vinyl polymer hybrid (A) substantially free of radiation-curable ethylenically unsaturated bonds means that the polyurethane-vinyl polymer hybrid (A) present in the aqueous radiation-curable coating composition of the present invention has a radiation-curable ethylenically unsaturated bond concentration (also referred to as C=C bond concentration) of less than 0.20 milliequivalents of C=C per gram of the hybrid (A), preferably less than 0.10 milliequivalents of C=C per gram of the hybrid (A), more preferably less than 0.05 milliequivalents of C=C per gram of the hybrid (A), and more preferably less than 0.01 milliequivalents of C=C per gram of the hybrid (A). As used herein, the amount of radiation-curable ethylenically unsaturated bonds in the hybrid (A) is measured by iodometric titration, i.e., by titration after adding a fixed excess of dodecyl mercaptan solution (0.25 N) on the unsaturated groups (isopropanol IPA / toluene as solvent, KOH as catalyst); it is allowed to react for 3 minutes (base-catalyzed Michael addition of the mercaptan to the double bond). Acetic acid is then added to neutralize the KOH, and an excess of iodine solution (0.1 N) is added on the dodecyl mercaptan. The residual iodine is then titrated with sodium thiosulfate using a platinum electrode. Most preferably, the hybrid (A) does not contain radiation-curable ethylenically unsaturated bonds.
[0102] Radiation curable diluent (B)
[0103] The aqueous radiation-curable coating composition comprises at least one radiation-curable diluent (B) having a molar mass of less than 750 g / mol and having an acrylate functionality of 2 to 5, preferably 2 to 4. The molar mass of the radiation-curable diluent (B) is calculated from its corresponding molecular formula, which indicates the number of atoms of each type in the radiation-curable diluent. Thus, the molar mass of (B) is the calculated molar mass obtained by adding the atomic masses of all atoms present in the structural formula of the compound.
[0104] In a preferred embodiment of the present invention, at least 20 wt. %, more preferably at least 30 wt. %, more preferably at least 40 wt. %, more preferably at least 50 wt. %, more preferably at least 60 wt. %, more preferably at least 70 wt. %, more preferably at least 80 wt. %, more preferably at least 90 wt. %, and most preferably 100 wt. % of the radiation curable diluent (B) is selected from:
[0105] With the corresponding molecular formula C 24 H 34 O9 and its corresponding di(trimethylolpropane)tetraacrylate (di-TMPTA) with a molar mass of 467 g / mol,
[0106] di(trimethylolpropane)tetraacrylate containing an alkoxy group,
[0107] With the corresponding molecular formula C 21 H 32 O8 and its corresponding di(trimethylolpropane) triacrylate (di-TMP3A) with a molar mass of 412 g / mol,
[0108] di(trimethylolpropane) triacrylate containing an alkoxy group,
[0109] With the corresponding molecular formula C 21 H 32 O9 and its corresponding glyceryl propoxy triacrylate (GPTA) with a molar mass of 428 g / mol,
[0110] Glyceryl propoxy triacrylate containing an additional alkoxy group,
[0111] With the corresponding molecular formula C 17 H 20 O8 and its corresponding pentaerythritol tetraacrylate (PET4A) with a molar mass of 352 g / mol,
[0112] Pentaerythritol tetraacrylate containing an alkoxy group,
[0113] With the corresponding molecular formula C 14 H 18 O7 and its corresponding pentaerythritol triacrylate (PET3A) with a molar mass of 298 g / mol,
[0114] Pentaerythritol triacrylate containing an alkoxy group,
[0115] With the corresponding molecular formula C 15 H 20 O6 and its corresponding trimethylolpropane triacrylate (TMPTA) with a molar mass of 296 g / mol,
[0116] trimethylolpropane triacrylate containing an alkoxy group,
[0117] With the corresponding molecular formula C 12 H 18 O5 and its corresponding dipropylene glycol diacrylate (DPGDA) with a molar mass of 242 g / mol,
[0118] Dipropylene glycol diacrylate containing an additional alkoxy group,
[0119] and any mixture thereof.
[0120] In case the radiation-curable diluent (B) comprises (additional) alkoxy groups, the maximum number of alkoxy groups is such that the molar mass remains below 750 g / mol.
[0121] In a more preferred embodiment of the present invention, at least 10 wt. %, more preferably at least 20 wt. %, more preferably at least 30 wt. %, more preferably at least 40 wt. %, most preferably at least 50 wt. %, more preferably at least 60 wt. %, more preferably at least 70 wt. %, more preferably at least 80 wt. %, more preferably at least 90 wt. %, and most preferably 100 wt. % of the radiation curable diluent (B) is selected from:
[0122] With the corresponding molecular formula C 24 H 34 O9 and its corresponding di(trimethylolpropane)tetraacrylate (di-TMPTA) with a molar mass of 467 g / mol,
[0123] di(trimethylolpropane)tetraacrylate containing an alkoxy group,
[0124] With the corresponding molecular formula C 21 H 32 O8 and its corresponding di(trimethylolpropane) triacrylate (di-TMP3A) with a molar mass of 412 g / mol,
[0125] di(trimethylolpropane) triacrylate containing an alkoxy group,
[0126] With the corresponding molecular formula C 21 H 32 O9 and its corresponding glyceryl propoxy triacrylate (GPTA) with a molar mass of 428 g / mol,
[0127] Glyceryl propoxy triacrylate containing an additional alkoxy group,
[0128] With the corresponding molecular formula C 15 H 20 O6 and its corresponding trimethylolpropane triacrylate (TMPTA) with a molar mass of 296 g / mol,
[0129] trimethylolpropane triacrylate containing an alkoxy group,
[0130] With the corresponding molecular formula C 12 H 18 O5 and its corresponding dipropylene glycol diacrylate (DPGDA) with a molar mass of 242 g / mol,
[0131] Dipropylene glycol diacrylate containing an additional alkoxy group,
[0132] and any mixture thereof.
[0133] Preferably, at least one radiation-curable diluent (B) has an acrylate functionality of 2 or 3, since this can advantageously lead to a more pronounced matting effect. The radiation-curable diluent (B) having an acrylate functionality of 2 is preferably selected from dipropylene glycol diacrylate (DPGDA) (having the corresponding molecular formula C 12 H 18 O5 and its corresponding molar mass 242g / mol); dipropylene glycol diacrylate containing additional alkoxy groups, preferably propoxy groups; and any mixture thereof.
[0134] The radiation-curable diluent (B) having an acrylate functionality of 3 is preferably selected from glyceryl propoxy triacrylate (GPTA) (having the corresponding molecular formula C 21 H 32 O9 and its corresponding molar mass 428g / mol); glyceryl propoxy triacrylate containing an additional alkoxy group, preferably a propoxy group; trimethylolpropane triacrylate (TMPTA) (having the corresponding molecular formula C 15 H 20 O6 and its corresponding molar mass 296g / mol); trimethylolpropane triacrylate containing alkoxy groups, preferably propoxy groups; having the corresponding molecular formula C 21 H 32 O8 and its corresponding di(trimethylolpropane) triacrylate (di-TMP3A) with a molar mass of 412 g / mol, di(trimethylolpropane) triacrylate containing an alkoxy group, preferably a propoxy group; pentaerythritol triacrylate (PET3A) (having the corresponding molecular formula C 14 H 18 O7 and its corresponding molar mass 298g / mol); pentaerythritol triacrylate containing alkoxy groups, preferably propoxy groups; and any mixtures thereof. The radiation-curable diluent (B) having an acrylate functionality of 2 or 3 preferably contains alkoxy groups, preferably propoxy groups (-C3H6O-).
[0135] Preferably, the composition further comprises at least one radiation-curable diluent (B) having an acrylate functionality of 4 or 5, since this advantageously can lead to further improved chemical resistance. The radiation-curable diluent (B) having an acrylate functionality of 4 is preferably selected from di(trimethylolpropane)tetraacrylate (di-TMPTA) (having the corresponding molecular formula C 24 H 34 O9 and its corresponding molar mass 467g / mol); di(trimethylolpropane) tetraacrylate containing alkoxy groups, preferably propoxy groups; pentaerythritol tetraacrylate (PET4A) (having the corresponding molecular formula C 17 H 20O8 and its corresponding molar mass 352g / mol); pentaerythritol tetraacrylate containing alkoxy groups, preferably propoxy groups; and any mixture thereof.
[0136] The radiation-curable diluent (B) having an acrylate functionality of 5 is preferably a diluent having the corresponding formula C 25 H 32 O 12 and dipentaerythritol pentaacrylate (DPPA) with a corresponding molar mass of 525 g / mol.
[0137] In a preferred embodiment, the aqueous radiation curable coating composition used in the process of the present invention comprises at least two radiation curable diluents (B), and the radiation curable diluents (B) present in the aqueous radiation curable coating composition have 2 to 4, preferably 2 to 3, diluents according to the formula The average acrylate functionality of k is the molar mass M present in the aqueous radiation curable coating composition. k And has acrylate functionality f k The amount of acrylate diluent (B) in g. We illustrate the calculation of the average acrylate functionality using a theoretical example:
[0138] For a formulation consisting of 60 g of a polyurethane-vinyl polymer mixture, 30 g of DPGDA (molar mass 242 g / mol, acrylate functionality 2), 10 g of Di-TMPTA (molar mass 466 g / mol, acrylate functionality 4) and 2.5 g of a photoinitiator: The sum of component k includes only DPGDA and Di-TMPTA, and the calculated average functionality of the acrylate diluent for this theoretical formulation is
[0139] The aqueous radiation curable coating composition used in the process may further comprise an acrylate diluent having a molar mass as defined by the (B) compound present in the radiation curable coating composition (i.e. below 750 g / mol), but having an acrylate functionality different from that defined by (B), for example an acrylate functionality of 6. However, such acrylate diluent may only be present in the aqueous radiation curable coating composition in such an amount that the average acrylate functionality of the acrylate diluent having a molar mass as defined by (B) (i.e. below 750 g / mol) is preferably from 2 to 5, more preferably from 2 to 4, even more preferably from 2 to 3.
[0140] Preferably, the aqueous radiation curable coating composition used in the process of the present invention comprises a monofunctional diluent in an amount of less than 7 wt.-%, more preferably less than 5 wt.-%, more preferably less than 3 wt.-%, more preferably less than 1 wt.-%, most preferably less than 0.5 wt.-% relative to the weight of the entire aqueous radiation curable coating composition.
[0141] In an even more preferred embodiment of the present invention, at least 60 wt. %, preferably at least 70 wt. %, more preferably at least 80 wt. %, more preferably at least 90 wt. %, and most preferably 100 wt. % of the radiation curable diluent (B) is a mixture of the following components:
[0142] (1) With the corresponding molecular formula C 24 H 34 O9 and its corresponding di(trimethylolpropane) tetraacrylate (di-TMPTA) with a molar mass of 467 g / mol and / or di(trimethylolpropane) tetraacrylate containing alkoxy groups, preferably propoxy groups and / or di(trimethylolpropane) tetraacrylate with the corresponding molecular formula C 17 H 20 O8 and its corresponding pentaerythritol tetraacrylate (PET4A) with a molar mass of 352 g / mol and / or pentaerythritol tetraacrylate containing alkoxy groups, preferably propoxy groups, and
[0143] (2) With the corresponding molecular formula C 21 H 32 O9 and its corresponding molar mass 428g / mol glyceryl propoxy triacrylate (GPTA) and / or glyceryl propoxy triacrylate containing additional alkoxy groups, preferably propoxy groups and / or dipropylene glycol diacrylate (DPGDA) and / or dipropylene glycol diacrylate containing additional alkoxy groups, preferably propoxy groups.
[0144] The radiation curable diluent (B) is added after free radical polymerization of the vinyl monomers to obtain the vinyl polymer of the polyurethane-vinyl polymer hybrid (A); and the polyurethane is preferably prepared in the presence of at least a portion of the one or more vinyl monomers used to prepare the vinyl polymer.
[0145] In the present invention, the polyurethane-vinyl polymer hybrid (A) preferably has a number average molecular weight M of at least 10 kg / mol, preferably at least 15 kg / mol, more preferably at least 20 kg / mol, and even more preferably at least 30 kg / mol. nThe polyurethane-vinyl polymer hybrid (A) preferably has a weight average molecular weight M of at least 50 kg / mol, preferably at least 100 kg / mol, more preferably at least 150 kg / mol, more preferably at least 200 kg / mol, more preferably at least 300 kg / mol, more preferably at least 400 kg / mol, and most preferably at least 500 kg / mol. w And may even be higher than the highest weight average molecular weight measurable using the method for determining weight average molecular weight as used herein. n and weight average molecular weight M w Determined as further described herein.
[0146] The amounts of (A) and (B) in the aqueous radiation-curable coating composition can vary within wide ranges, since water and optionally organic solvents can be used to adopt the viscosity and to adjust the layer thickness of the applied coating. Preferably, the amount of (A) is 35 to 80% by weight and the amount of (B) is 20 to 65% by weight, based on the total amount of (A) and (B), more preferably the amount of (A) is 40 to 80% by weight and the amount of (B) is 20 to 60% by weight.
[0147] The total amount of (A) and (B) is preferably 10 to 60 wt%, more preferably 15 to 50 wt%, more preferably 15 to 45 wt%, even more preferably 20 to 40 wt%, even more preferably 25 to 35 wt%, based on the total weight of the aqueous radiation curable coating composition.
[0148] The amount of water in the aqueous radiation curable coating composition is preferably at least 30 wt%, or at least 35 wt%, or at least 40 wt%, or at least 45 wt%, or at least 50 wt%, or at least 55 wt%, or at least 60 wt%, or at least 70 wt%, based on the total weight of the aqueous radiation curable coating composition.
[0149] The optional organic solvent is present in an amount of up to 30% by weight, preferably up to 25% by weight, more preferably up to 20% by weight, more preferably up to 15% by weight, more preferably up to 10% by weight, more preferably up to 5% by weight, more preferably up to 4% by weight, more preferably up to 3% by weight, more preferably up to 2% by weight, more preferably up to 1% by weight, wherein the amount of the organic solvent is based on the total amount of water and organic solvent present in the aqueous radiation-curable coating composition. Suitable organic solvents are solvents that are inert to the functional groups present in the coating composition. Suitable solvents are, for example, hydrocarbons, alcohols, ketones and esters, such as cosolvents that also have the function of a coalescing agent, such as 1-methyl-2-pyrrolidone, glycols and glycol ethers, such as alkyl ethers of butyl diglycol, dipropylene glycol methyl ether, acetone, methyl ethyl ketone and glycol acetate or mixtures thereof, and ester alcohols, such as 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (Texanol). Most preferably, the aqueous radiation curable coating composition is substantially free of organic solvents, ie preferably no organic solvents are intentionally added to the aqueous radiation curable coating composition (ie small amounts of organic solvents may be present in additives used to prepare the composition).
[0150] (A) and (B) together preferably have a radiation-curable ethylenically unsaturated bond concentration of 0.8 to 5.0 milliequivalents (meq) C=C / g (A)+(B), preferably 1.5 to 4 meq C=C / g (A)+(B). The amount of radiation-curable ethylenically unsaturated bonds in the hybrid (A) and the radiation-curable diluent (B) is measured by iodometric titration, i.e. by titration (isopropanol IPA / toluene as solvent and KOH as catalyst) after adding a fixed excess of dodecyl mercaptan solution (0.25 N) on the unsaturated groups; the reaction is allowed to react for 3 minutes (base catalyzed Michael addition reaction of the mercaptan to the double bond). Acetic acid is then added to neutralize the KOH and an excess of iodine solution (0.1 N) is added on the dodecyl mercaptan. The residual iodine is then titrated with sodium thiosulfate using a platinum electrode.
[0151] The total amount of the biobased carbon content in (A) and (B) relative to the total mass of carbon in (A) and (B), measured by method B according to standard ASTM D6866-12, is preferably at least 5% by weight, more preferably at least 10% by weight, more preferably at least 20% by weight, more preferably at least 30% by weight, most preferably at least 40% by weight relative to the total weight of (A) and (B).
[0152] The viscosity of the dispersion consisting of (A), (B) and (C) and containing 10 to 60 wt. % of (A) and (B), relative to the total amount of (A), (B) and (C), is preferably 10 to 1000 mPa.s, or 10 to 800 mPa.s, or 10 to 500 mPa.s. The viscosity is determined as further described herein.
[0153] The z-average particle size of the dispersion consisting of (A), (B) and (C) is preferably from 20 to 1000 nm, more preferably from 25 to 500 nm, even more preferably from 25 to 250 nm, and most preferably from 30 to 200 nm, whereby the z-average particle size is determined as further described herein.
[0154] The aqueous radiation-curable coating composition of the present invention is preferably substantially free of tin and / or substantially free of tertiary amines. As used herein, substantially free of tin means that the radiation-curable coating composition contains preferably up to 50 ppm (relative to the aqueous radiation-curable coating composition), more preferably up to 10 ppm, more preferably up to 5 ppm, more preferably up to 2 ppm of tin, and more preferably, the aqueous radiation-curable coating composition of the present invention does not contain tin. As used herein, substantially free of tertiary amines means that the radiation-curable coating composition contains preferably up to 1.5 wt % (relative to the aqueous radiation-curable coating composition), more preferably up to 1 wt %, more preferably up to 0.5 wt %, more preferably up to 0.1 wt % of tertiary amines, such as triethylamine, and more preferably, the aqueous radiation-curable coating composition of the present invention does not contain tertiary amines.
[0155] The coating composition generally further contains an additive compound; that is, a collection of one or more than one individual additives having one or more than one specified structure or type. Suitable additives are, for example, light stabilizers, such as ultraviolet absorbers and reversible free radical scavengers (HALS), photosensitizers, antioxidants, degassing agents, wetting agents, emulsifiers, slip additives, waxes, inhibitors, adhesion promoters, flow control agents, film formers, rheological aids such as thickeners, flame retardants, corrosion inhibitors, waxes, desiccants and biocides. One or more of the above additives may be used in any suitable amount in the coating composition used in the method of the present invention, and may be selected individually or in combination of one or more types listed herein. In a preferred embodiment, the additive compound is present in an amount of about 0% to 40% by weight, or 0% to 30% by weight, or 0% to 20% by weight, or 0% to 10% by weight, or 0% to 5% by weight, or 0.01% to 40% by weight, or 0.01% to 30% by weight, or 0.01% to 20% by weight, or 0.01% to 10% by weight, or 0.01% to 5% by weight, or 0.1% to 2% by weight, relative to the total weight of the radiation curable coating composition. Another advantage of the present invention is that the coating composition can also be colored without significantly complicating the application of the coating composition on the substrate. The coating composition then contains at least one pigment. In the art, titanium dioxide (TiO2) is considered to be a commercially important white pigment. Despite the porous nature of pigments of this type, it has furthermore surprisingly been found that the presence of pigments of this type in the coating composition as defined herein hardly impairs the coffee, red wine and / or mustard resistance of the coating, or only deteriorates it to such an extent that the resistance to coffee, red wine and / or mustard remains at an acceptable level.
[0156] The coating composition may also contain one or more inorganic fillers. The coating composition may also contain external matting agents with an additional matting effect, but this is not preferred. Suitable external matting agents are, for example, inorganic silica or organic waxes. The maximum amount of external matting agent is preferably at most 1.5 wt. %, more preferably at most 1 wt. %, and most preferably at most 0.5 wt. %, relative to the total weight of the coating composition.
[0157] The present invention further relates to a process for preparing the aqueous radiation-curable coating composition of the present invention.
[0158] The method for preparing the aqueous radiation-curable coating composition of the present invention comprises preparing an aqueous radiation-curable dispersion of particles comprising a polyurethane-vinyl polymer hybrid (A), wherein a radiation-curable diluent (B) is added after free radical polymerization of the vinyl monomer to obtain the vinyl polymer of the polyurethane-vinyl polymer hybrid (A).
[0159] In a preferred embodiment of the present invention, wherein component (A2) comprises at least one dihydroxyalkanoic acid or consists essentially of at least one dihydroxyalkanoic acid or consists of at least one dihydroxyalkanoic acid, the process for preparing the aqueous radiation-curable coating composition preferably comprises
[0160] I. reacting components (A1), (A2) and (A4) and optionally (A3) and optionally (A5) to obtain a polyurethane prepolymer,
[0161] (a) blending a polyurethane prepolymer with an aqueous phase comprising a neutralizing agent and preferably comprising a nitrogen-containing chain extender compound (A6) to obtain a dispersion, or (b.1) neutralizing the polyurethane prepolymer by adding a neutralizing agent to the polyurethane prepolymer, and subsequently (b.2) adding the neutralized polyurethane prepolymer to water preferably comprising a nitrogen-containing chain extender compound (A6) to obtain a dispersion, or (b.2′) adding water preferably comprising a nitrogen-containing chain extender compound (A6) to the neutralized polyurethane prepolymer to obtain a dispersion, or (b.2″) adding the neutralized polyurethane prepolymer to water to obtain a dispersion, and then adding the nitrogen-containing chain extender compound (A6) to the dispersion, thereby
[0162] Adding vinyl monomers before, during or after the preparation of the polyurethane,
[0163] Adding a free radical initiator to polymerize the vinyl monomer in the presence of the polyurethane, and
[0164] After free radical polymerization of the vinyl monomers, a radiation curable diluent (B) is added to obtain the vinyl polymer of the polyurethane-vinyl polymer hybrid (A).
[0165] Any of the foregoing steps may be performed in the presence of a temporary solvent such as acetone or MEK removed from the aqueous polyurethane-vinyl polymer hybrid (A) dispersion.
[0166] Step I is preferably carried out in the presence of at least a portion of the one or more vinyl monomers used to prepare the vinyl polymer.
[0167] In a preferred embodiment of the present invention in which component (A2) comprises at least one diamine sulfonate or consists essentially of at least one diamine sulfonate or consists of at least one diamine sulfonate, the process for preparing the aqueous radiation-curable coating composition according to the present invention preferably comprises
[0168] I. reacting components (A1), (A4) and optionally (A3) and optionally (A5) to obtain a polyurethane prepolymer,
[0169] II. (II.1) adding a polyurethane prepolymer to water containing a diamine sulfonate (A2) and preferably a nitrogen-containing chain extender compound (A6) to obtain a dispersion, or (II.1') adding water containing a diamine sulfonate (A2) and preferably a nitrogen-containing chain extender compound (A6) and optionally further adding water to the polyurethane prepolymer to obtain a dispersion, thereby
[0170] Adding vinyl monomers before, during or after the preparation of the polyurethane,
[0171] Adding a free radical initiator to polymerize the vinyl monomer in the presence of the polyurethane, and
[0172] After free radical polymerization of the vinyl monomers, a radiation curable diluent (B) is added to obtain the vinyl polymer of the polyurethane-vinyl polymer hybrid (A).
[0173] Any of the foregoing steps may be performed in the presence of a temporary solvent such as acetone or MEK removed from the aqueous polyurethane-vinyl polymer hybrid (A) dispersion.
[0174] Step I is preferably carried out in the presence of at least a portion of the one or more vinyl monomers used to prepare the vinyl polymer.
[0175] The method of the present invention optionally includes a pre-curing step (2a). Carrying out the pre-curing step (2a) may be beneficial to improve adhesion, in particular to improve inter-coat adhesion. In this optional step (2a), pre-curing of the at least partially dried coating composition is achieved to provide an at least partially cured coating composition. In the optional step (2a), some reactive ethylenically unsaturated double bonds of the curable compound are polymerized in the uncured coating so that the coating is partially cured but not yet fully cured. This process is also referred to as pre-curing.
[0176] Therefore, the method of the present invention comprises the following steps in the order (1), (2), (2a), (3) and (4):
[0177] (1) applying an aqueous radiation-curable coating composition onto a surface of a substrate,
[0178] (2) drying the aqueous radiation-curable coating composition to provide an at least partially dried coating composition,
[0179] (2a) optionally by irradiating with ultraviolet light having a wavelength of 300 to 450 nm, preferably 300 to 420 nm, at a dose of 20 to 200 mJ / cm 2 The radiation dose is preferably 30 to 100 mJ / cm 2 irradiating the at least partially dried coating composition with a radiation dose of 1000 Å to pre-cure the at least partially dried coating composition to provide an at least partially cured coating composition,
[0180] (3) irradiating the at least partially dried coating composition or the at least partially cured coating composition with ultraviolet light having a wavelength of ≤220 nm, preferably a wavelength of ≥120 nm, more preferably ≥150 nm, and particularly preferably 172 nm or 195 nm under an inert atmosphere, and then
[0181] (4) Irradiation with ultraviolet light of wavelength ≥ 300 nm or electron beam.
[0182] In step (1) of the method of the present invention, the aqueous radiation-curable coating composition is applied to the substrate by methods known to those skilled in the art (e.g., knife coating, brush coating, roller coating, spray coating). The coating composition is applied to the substrate in a coating thickness (before drying) of preferably 5 to 300 microns, more preferably 15 to 175 microns, more preferably 20 to 150 microns, more preferably 25 to 125 microns.
[0183] In step (2) of the process of the present invention, the drying of the aqueous radiation curable coating composition applied to the substrate is preferably carried out at a temperature above 30° C. to evaporate water and optionally organic solvents and other volatile compounds to provide an at least partially dried coating composition. The term "drying" refers to the loss of water and, if present, organic solvents and other volatile compounds, such as neutralizing agent amines, from the aqueous coating composition by evaporation to such an extent that preferably at least 80% by weight of the water is removed.
[0184] The irradiation in the optional pre-curing step (2a) is preferably carried out under atmospheric conditions, in other words not under inert gas conditions and / or not in an oxygen-reduced atmosphere. Suitable radiation sources for the ultraviolet light in the specified wavelength range in step (2a) are UV-A emitting radiation sources (e.g. fluorescent tubes, LED lamps), high-pressure or medium-pressure mercury vapor lamps (wherein the mercury vapor can be modified by doping with other elements such as gallium or iron), pulsed lamps (so-called UV flash lamps) or halogen lamps. In a preferred embodiment of the present invention, the process is carried out without step (2a), i.e. the curing of the radiation-curable coating composition is carried out in only two irradiation steps, i.e. steps (3) and (4)).
[0185] A suitable radiation source for step (3) is an excimer ultraviolet lamp, which emits ultraviolet light with a wavelength of ≤220 nm, preferably ≥120 nm, more preferably ≥150 nm, and particularly preferably 172 nm or 195 nm. The radiation dose used in step (3) is generally in the range of 0.1 to 150 mJ / cm 2 , preferably 1 to 100 mJ / cm 2 , more preferably 1 to 20 mJ / cm 2 , more preferably 2 to 15 mJ / cm 2 . Step (3) must be carried out in an inert gas atmosphere. An inert gas atmosphere is understood to mean an essentially oxygen-free atmosphere, i.e. an atmosphere containing less than 0.5% by volume of oxygen, preferably less than 0.1% by volume of oxygen, and particularly preferably less than 0.05% by volume of oxygen. Typically, an inert gas atmosphere is achieved by purging the area exposed to UV radiation with an inert gas stream. An inert gas atmosphere prevents unwanted ozone formation on the one hand, and prevents the polymerization of the paint layer from being inhibited on the other hand. Examples of inert gases are nitrogen, helium, neon or argon. Particularly preferably, nitrogen is used. This nitrogen should contain only very small amounts of foreign gases, such as oxygen, preferably with a purity grade of <300 ppm oxygen.
[0186] In step (4) of the method of the present invention, the coating obtained in step (3) is irradiated with ultraviolet light having a wavelength ≥ (higher than or equal to) 300 nm or with electron beams to achieve a major or preferably complete polymerization of the radiation curable compounds of the coating composition, so that the coating is preferably completely cured. In the case of applying electron beam irradiation (150 to 300 kV) in step (4), a dose of 10 to 100 kGy, preferably 20 to 50 kGy, is generally applied. In step (4), ultraviolet irradiation is preferred, preferably with a wavelength of 300 to 420 nm and preferably with a power of 100 to 2000 mJ / cm 2 , more preferably 150 to 1500 mJ / cm 2 The radiation dose of the coating composition can be 0.1 to 5% by weight of the coating composition. Preferably, the one or more photoinitiators are present in an amount of 0.25% to 4% by weight, more preferably 0.5% to 3.5% by weight, and even more preferably 0.5% to 3% by weight, relative to the total weight of the coating composition.
[0187] Photoinitiator is a compound that chemically changes to produce at least one of free radicals, acids and bases due to the action of light or the synergistic effect between the action of light and the electronic excitation of the sensitizing dye. Known photoinitiator types include cationic photoinitiators and free radical photoinitiators. According to one embodiment of the present invention, the photoinitiator is a free radical photoinitiator.
[0188] In one embodiment, the photoinitiator compound includes, consists of, or consists essentially of one or more acylphosphine oxide photoinitiators. Acylphosphine oxide photoinitiators are known and disclosed, for example, in U.S. Pat. Nos. 4,324,744, 4,737,593, 5,942,290, 5,534,559, 6,020,529, 6,486,228, and 6,486,226. Preferred types of acylphosphine oxide photoinitiators for the photoinitiator compound include bisacylphosphine oxide (BAPO) or monoacylphosphine oxide (MAPO). More specifically, examples include 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide (CAS#84434-11-7) or 2,4,6-trimethylbenzoyldiphenylphosphine oxide (CAS#127090-72-6).
[0189] In a preferred embodiment, the photoinitiator compound may also optionally comprise, consist of, or consist essentially of an α-hydroxyketone photoinitiator. For example, suitable α-hydroxyketone photoinitiators are α-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropanone, 2-hydroxy-2-methyl-1-(4-isopropylphenyl)propanone, 2-hydroxy-2-methyl-1-(4-dodecylphenyl)propanone, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one, and 2-hydroxy-2-methyl-1-[(2-hydroxyethoxy)phenyl]propanone.
[0190] In another embodiment, the photoinitiator compound comprises, consists of, or consists essentially of: α-amino ketones, such as 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-(4-methylbenzyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl]-1-butanone, or 2-benzyl-2-(dimethylamino)-1-[3,4-dimethoxyphenyl]-1-butanone; benzophenones, such as benzophenone, 2,4,6-trimethylbenzophenone, 4-methylbenzophenone, 2-methylbenzophenone, 2-methoxycarbonyldi ... benzophenone, 4,4'-bis(chloromethyl)-benzophenone, 4-chlorobenzophenone, 4-phenylbenzophenone, 4,4'-bis(dimethylamino)-benzophenone, 4,4'-bis(diethylamino)benzophenone, 2-benzoylbenzoic acid methyl ester, 3,3'-dimethyl-4-methoxybenzophenone, 4-(4-methylphenylthio)benzophenone, 2,4,6-trimethyl-4'-phenyl-benzophenone or 3-methyl-4'-phenyl-benzophenone; ketal compounds, for example 2,2-dimethoxy-1,2-diphenyl-ethanone; and monomeric or dimeric benzoylformates, such as methylbenzoylformate, 5,5'-oxy-bis(ethyleneoxydicarbonylphenyl) or 1,2-(benzoylcarboxy)ethane.
[0191] Other suitable photoinitiators for use in the photoinitiator compound include oxime esters, such as those disclosed in US Pat. No. 6,596,445. Yet another class of suitable photoinitiators for use in the photoinitiator compound include, for example, phenyl glyoxylates, such as those disclosed in US Pat. No. 6,048,660.
[0192] In another embodiment, the photoinitiator compound may comprise, consist of, or consist essentially of one or more alkyl-, aryl-, or acyl-substituted compounds not mentioned above.
[0193] According to another embodiment, the composition may contain a photoinitiator that is an alkyl-, aryl- or acyl-substituted compound. In one embodiment, the alkyl-, aryl- or acyl-substituted photoinitiator has or is centered on an atom in the carbon group (Group 14). In this case, upon excitation (by absorbing radiation), the Group 14 atoms present in the photoinitiator compound form free radicals. Such compounds can therefore produce free radicals having or being centered on an atom selected from silicon, germanium, tin and lead. In one embodiment, the alkyl-, aryl- or acyl-substituted photoinitiator is an acylgermanium compound. Such photoinitiators are described in US9708442. Known specific acylgermanium photoinitiators include benzoyltrimethylgermane (BTG), tetraacylgermane or bisacylgermane (which can be used as Commercially available from Ivoclar Vivadent AG, 9494 Schaan / Liechtenstein).
[0194] Photoinitiators can be used alone or in combination as a blend. Suitable photoinitiator blends are disclosed, for example, in U.S. Patent No. 6,020,528 and U.S. Patent Application No. 60 / 498,848. According to one embodiment, the photoinitiator compound includes, for example, a photoinitiator blend of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (CAS#162881-26-7) and 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide (CAS#84434-11-7) in a weight ratio of about 1:11, 1:10, 1:9, 1:8 or 1:7.
[0195] Another particularly suitable photoinitiator blend is a mixture of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide and 2-hydroxy-2-methyl-1-phenyl-1-propanone (CAS#7473-98-5), for example, in a weight ratio of about 3:1:15 or 3:1:16 or 4:1:15 or 4:1:16. Another suitable photoinitiator blend is a mixture of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2-hydroxy-2-methyl-1-phenyl-1-propanone, for example, in a weight ratio of about 1:3, 1:4 or 1:5.
[0196] One or more of the above-mentioned photoinitiators may be used in the photoinitiator compound in the composition according to the invention in any suitable amount and may be selected individually or in combination of one or more types listed herein. In a preferred embodiment, the photoinitiator compound comprises, consists of or consists essentially of a free radical photoinitiator, which is preferably of the α-cleavage type.
[0197] Suitable substrates for the method according to the invention are, for example, mineral substrates, such as fiber cement boards, wood, wood-containing materials, paper (including paperboard), textiles, leather, metals, thermoplastic polymers, thermosetting materials, ceramics, glass. Suitable thermoplastic polymers are, for example, polyvinyl chloride PVC, polymethyl methacrylate PMMA, acrylonitrile-butadiene-styrene ABS, polycarbonate, polypropylene PP, polyethylene PE, polyamide PA, polyethylene terephthalate PET and polystyrene PS. Suitable thermosetting materials are, for example, linoleum, epoxy resins, melamine, novolac resins, polyesters and urea-formaldehyde.
[0198] The substrate is optionally pretreated and / or optionally precoated. For example, a thermoplastic film may be treated with a corona discharge or precoated with a primer prior to application. Mineral building materials are also typically provided with a primer prior to application of the coating composition.
[0199] The coatings obtained in the process of the invention can advantageously be used for floor or wall coverings or for automotive interiors or furniture.
[0200] Using the method of the present invention, a low gloss coating having a dry thickness of at least 2 microns, or at least 3 microns, or at least 4 microns, and at most 100 microns, or at most 75 microns, or at most 50 microns can be advantageously obtained.
[0201] The present invention further relates to an aqueous radiation curable coating composition as described above. The present invention further relates to a coated substrate obtained by coating a substrate with a process as described above.
[0202] The invention will now be illustrated with reference to the following examples. Unless otherwise indicated, all parts, percentages and ratios are by weight.
[0203] Measurement method
[0204] Average particle size PS:
[0205] The intensity average particle size, z-average, was determined by photon correlation spectroscopy using a Malvern Zetasizer Nano ZS. The sample was diluted in demineralized water to a concentration of approximately 0.1 g dispersion / liter. The measurement temperature was 25°C. The laser incident angle was 173°. The laser wavelength was 633 nm.
[0206] pH
[0207] The pH was measured using a Metrohm pH meter.
[0208] Solid content
[0209] The solids content of the dispersions was measured on a HB43-S halogen moisture analyzer from Mettler Toledo at a temperature of 75°C.
[0210] Viscosity
[0211] Viscosity was measured using a Brookfield LV (spindle 2 at 60 rpm, room temperature).
[0212] Number average molecular weight, weight average molecular weight, z average molecular weight and molecular weight distribution
[0213] The number average molecular weight, weight average molecular weight, z average molecular weight and molecular weight distribution were determined by size exclusion chromatography at 70°C using three PLgel 10μm Mixed-BPFG columns on a Waters Alliance 2695LC system with a Waters 2410DRI detector and a Waters 2996PDA detector. Dimethylformamide (DMF) containing 10mmol lithium bromide (LiBr) was used as the eluent with a flow rate of 1mL / min. The sample was dissolved in the eluent using a concentration of 5mg polymer / mL solvent. The solubility was judged with a laser pointer after stabilization for 24 hours at room temperature; if any scattering was visible, the sample was first filtered using a 0.45μm PTFE filter and 150μl of the sample solution was injected. M was calculated using narrow polystyrene standards from 474 to 1.730.000Da supplied by Agilent. n (number average molecular weight), M W (weight average molecular weight) and MWD (molecular weight distribution) results.
[0214] Generally, a series of average molecular weights can be defined by the following equation: M = ∑N i M n+1 / ∑N i M i n , from which: n = 0, we get M = M n ; n = 1 gives M = Mw, n = 2 gives M = M z Higher average values are increasingly sensitive to high molecular weight polymers. i The molecular weight is M i The number of molecules.
[0215] Glossiness
[0216] Gloss is measured in the drawdown direction according to ISO 2813 and is expressed in gloss units (GU).
[0217] Stain resistance
[0218] Coffee, red wine and mustard tolerance were determined colorimetrically using an eXact standard handheld spectrophotometer from X-rite and are reported in Tables 5 and 6. For coffee, the spots were exposed for 1 hour, 6 hours and rated after 24 hours. For red wine and mustard, the spots were exposed for 6 hours and rated after 24 hours. a- and b-values were measured according to ISO 7724. Coffee and mustard tolerance was determined by Δb values, where Δb value = b (分别在咖啡暴露6小时和1小时或芥末暴露6小时后并在24小时后评级) –b (暴露前) A higher Δb value indicates a greater color change caused by staining, and therefore poor stain resistance. Red wine resistance is determined using the Δa value colorimetrically, where Δa value = a (在红酒暴露6小时后并在24小时后评级) -a (暴露前) A higher Δa value indicates a greater color change caused by staining, and therefore poor stain resistance. The a* axis is relative to the green-red color opposition, with negative values tending toward green and positive values tending toward red. The b* axis represents the blue-yellow color opposition, with negative numbers tending toward blue and positive numbers tending toward yellow.
[0219] Method for calculating urea content in polyurethane
[0220] As known to those skilled in the art, the concentration of urea bonds in the polyurethane in meq / g solids is determined by calculation according to the formula given below.
[0221] Urea content PU(A)=(((total NCO-total OH-total NH x )*ED*(AF CE / AH CE ))+((Total NCO-Total OH-Total NH x )*(1-ED)*0,5)+total NH x )*1000 / W PU(A)
[0222] in
[0223] Total NCO: the number of NCO groups in moles originating from component (A1),
[0224] Total OH: number of alcohol groups in moles from components (A2) to (A5),
[0225] Total NH x : The molar amount of amine (NH x , where x = 1 or 2) the total number of groups,
[0226] W PU(A) : the total weight of the polyurethane [components (A1) to (A6)] in grams,
[0227] ED: chain extension degree: the molar ratio of active hydrogen in the nitrogen-containing chain extender (A6) to the theoretical residual isocyanate groups in the polyurethane prepolymer (= total NCO-total OH-total NH x ),
[0228] AH CE : The number of active hydrogen atoms in the nitrogen-containing chain extender (A6), where each NH x (where x = 1 or 2) The functionality is counted as one active hydrogen, except for hydrazides where the NH group attached to the carbonyl is not considered a chain extending group.
[0229] AF CE : NH of nitrogen-containing chain extender (A6) x A functionality where x = 1 or 2 and where for hydrazide, the NH group attached to the carbonyl group is not considered a chain extending group.
[0230] We illustrate this calculation with the following theoretical example.
[0231] Calculation of the urea group content in the polyurethanes used in theoretical examples I to VI
[0232]
[0233] Method for calculating dry film thickness
[0234] The dry film thickness is calculated by multiplying the wet film thickness by the solids content of the formulation used.
[0235] DFT = WFT * solid content / 100
[0236] in
[0237] DFT: Dry film thickness in μm
[0238] WFT: wet film thickness in μm
[0239] Solid content (wt%): total weight of all solid compounds present in a formulation divided by (total weight of the formulation*100).
[0240] Components and abbreviations used :
[0241] IPDI = isophorone diisocyanate available from Covestro
[0242] HDI = Hexane diisocyanate available from Covestro
[0243] W = DesW = HMDI = dicyclohexylmethane diisocyanate available from Covestro
[0244] DMPA = dimethylolpropionic acid available from Perstorp polyols
[0245] PPG2000 = 1,2-polypropylene glycol available from BASF, OH value = 56 mg KOH / g Velvetol H2000 = 1,3-polypropylene glycol available from Alessa, OH value = 56 mg KOH / g
[0246] Priplast 3192 = polyester polyol available from Croda, OH value = 56 mg KOH / g
[0247] pTHF650 = polytetramethylene glycol available from BASF, OH value = 173 mg KOH / g
[0248] Ymer TM N120 = nonionic diol available from Perstorp, OH value = 110 mg KOH / g
[0249] MMA = Methyl Methacrylate
[0250] BA = n-butyl acrylate
[0251] OA = 2-octyl acrylate
[0252] NPG = neopentyl glycol available from Perstorp
[0253] TEA = triethylamine from Arkema
[0254] DPGDA=Agisyn TM 2833, dipropylene glycol diacrylate available from Covestro
[0255] GPTA=Agisyn TM 2837, propoxylated (3) glyceryl triacrylate available from Covestro
[0256] DiTMPTA=Agisyn TM 2887TF, ditrimethylolpropane tetraacrylate available from Covestro
[0257] EO-PETiA=Agisyn TM 2844, ethoxylated (5) pentaerythritol tetraacrylate available from Covestro
[0258] DPHA=Agisyn TM 2830L = dipentaerythritol hexaacrylate available from Covestro
[0259] EGDMA = ethylene glycol dimethacrylate available from Covestro
[0260] BHT = Butylated hydroxytoluene available from Brenntag
[0261] Hydrazine = Hydrazine hydrate available from Arkema (16%)
[0262] Vestamin A 95 = Sodium N-(2-aminoethyl)aminoethanesulfonate available from Evonik (51% w / w aqueous solution)
[0263] EDA = ethylenediamine available from Caldic
[0264] Bismuth ND = bismuth neodecanoate catalyst available from Reaxis
[0265] Omnirad 500 = photoinitiator available from IGM
[0266] BYK 346 = surfactant available from BYK
[0267] BYK011 = defoamer available from BYK
[0268] Butyl glycol = solvent available from Aldrich
[0269] Airex 902W = defoamer available from Evonik
[0270] Gel L 75N = rheology modifier available from Borchers
[0271] TS100 = Silica matting agent from Evonik
[0272] Preparation of polyurethane dispersion (PUD 1)
[0273] A 2000 cm 3 The flask was charged with components DMPA (37.4 g), PPG2000 (23.4 g) and IPDI (163.0 g). The reaction was heated to 50°C. Then 0.04 g of bismuth neodecanoate was added. After the exotherm was complete, the reaction was maintained at 90°C for 120 minutes. The NCO content of the resulting isocyanate-terminated prepolymer was 3.16% (theoretical 3.29%). The prepolymer was cooled to 80°C and TEA (28.3 g) was added and mixed at 80°C for 10 minutes.
[0274] A dispersion of the resulting isocyanate-terminated prepolymer was prepared by feeding 500 g of the resulting prepolymer mixture into deionized water (850 g) containing 0.5 g of Tegofoamex 805 over 45 minutes.
[0275] The temperature of the dispersion was controlled between 25 and 30° C. Hydrazine (32.4 g of a 16% aqueous solution) was added after the feeds were complete. The solids content of the resulting dispersion was 34.2% by weight.
[0276] Preparation of polyurethane-vinyl polymer hybrid resin dispersions (UAEx.1-4 and UA Ex.11-12)
[0277] In nitrogen atmosphere at 1000 cm 3 In a flask, 319.1 g of the dispersion prepared in stage 1 (PUD 1) was mixed with 43.7 g of deionized water, 27.4 g of MMA and 0.5 g of BA. After 45 minutes, tert-butyl hydroperoxide tBHPO (0.8 g (10% aqueous solution)) and Fe(II)EDTA (0.08 g (1% aqueous solution)) were added. Subsequently, an aqueous solution of iAA (isoascorbic acid) neutralized with ammonia (1%, 8.4 g) was slowly added to the PU dispersion through a dropping funnel over 15 minutes. The resulting polyurethane-vinyl polymer hybrid dispersion had a solid content of 34.4 wt% solids and a pH of 7.8.
[0278] Table 1 specifies the components and amounts used to prepare the polyurethane-vinyl polymer hybrid resin dispersions of UA Examples 1-4 and 11 and 12. Unless otherwise indicated, the amounts of the various components are expressed in grams.
[0279] Table 1: Composition of UA Ex.1-4 and UA Ex.11 and 12
[0280]
[0281] Preparation of polyurethane vinyl polymer hybrid resin dispersion (UA Ex.5)
[0282] A 2000 cm 3The components PPG2000 (189.8 g), NPG (12.5 g) and IPDI (71.5 g) were charged into the flask. The reaction was heated to 50° C. and 0.03 g of bismuth neodecanoate was added. After the exotherm was complete, the reaction was maintained at 95° C. for 120 minutes. The mixture was cooled to 40° C. and 410 g of acetone was added. The NCO content of the obtained isocyanate-terminated prepolymer solution was 1.26%. A mixture of EDA (2.5 g) and Vestamin A95 (19.4 g) was added over 15 minutes. A dispersion was subsequently prepared by adding water (522 g). BYK011 (0.03 g) was then added and acetone was removed from the dispersion by vacuum distillation. The solid content of the obtained PUD was 34.6% by weight.
[0283] Under nitrogen atmosphere, 25 g of water, 13.3 g of MMA and 4.1 g of BA were added to 200 g of the resulting dispersion and mixed at room temperature for 45 minutes. Subsequently, 0.52 g of 10% tBHPO solution and 0.05 g of 1% Fe(II)EDTA solution were added. Finally, 5.2 g of 1% isoascorbic acid solution was added to the dispersion over 10 minutes. The specifications of the resulting polyurethane-vinyl polymer hybrid are shown in Table 2.
[0284] Preparation of polyurethane-vinyl polymer hybrid resin dispersion (UAEx.6)
[0285] A 2000 cm 3 The components PPG2000 (168.6 g), DMPA (14.9) and IPDI (64.9 g) were charged into the flask. The reaction was heated to 50°C and 0.03 g of bismuth neodecanoate was added. After the exotherm was complete, the reaction was maintained at 95°C for 120 minutes. The mixture was cooled to 40°C and 62 g of acetone was added. The NCO content of the obtained isocyanate-terminated prepolymer solution was 2.33%. 15% KOH solution (29.1 g) was slowly added. A dispersion was then prepared by adding water (537 g). The isocyanate-terminated prepolymer chain was extended with water. BYK011 (0.04 g) was then added and acetone was removed from the dispersion by vacuum distillation. The solid content of the obtained PUD was 38.6 wt %.
[0286] To 181 g of the resulting dispersion was added 45 g of water, 13.3 g of MMA and 4.1 g of BA under nitrogen atmosphere and mixed at room temperature for 45 minutes. Subsequently, 0.52 g of a 10% tBHPO solution and 0.05 g of a 1% Fe(II)EDTA solution were added. Finally, 5.2 g of a 1% isoascorbic acid solution was added to the dispersion over 10 minutes. The specifications of the resulting polyurethane-vinyl polymer hybrid are listed in Table 2.
[0287] Preparation of polyurethane-vinyl polymer hybrid resin dispersion (UA Ex.7)
[0288] A 2000 cm 3 The flask was charged with components Velvetol H2000 (282.3 g), DMPA (25.0 g) and IPDI (108.7 g). The reaction was heated to 50°C and 0.04 g of bismuth neodecanoate was added. After the exotherm was complete, the reaction was maintained at 95°C for 120 minutes. The NCO content of the resulting isocyanate-terminated prepolymer was 3.14%. After cooling to 80°C, TEA (18.8 g) was added and mixed for 15 minutes.
[0289] 290 g of the obtained isocyanate-terminated prepolymer mixture was added to deionized water (502 g) within 45 minutes, and the dispersion temperature was controlled at 25-30° C. After the addition was completed, hydrazine (16% aqueous solution, 18.64 g) was added. The solid content of the obtained dispersion was 33.5% by weight.
[0290] To 209 grams of the resulting dispersion was added 18.2 g of water, 13.3 g of MMA and 4.1 g of OA under nitrogen atmosphere and mixed at room temperature for 45 minutes. Subsequently, 0.52 g of a 10% tBHPO solution and 0.05 g of a 1% Fe(II)EDTA solution were added. Finally, 5.2 g of a 1% isoascorbic acid solution (pH>7) was added to the dispersion over 10 minutes. The specifications of the resulting polyurethane-vinyl polymer hybrid are listed in Table 2.
[0291] Preparation of polyurethane-vinyl polymer hybrid resin dispersion (UA Ex.8)
[0292] A 1000 cm 3 The flask was charged with components DMPA (24.9 g), Priplast 3192 (353.1 g), MMA (125.2 g), BHT (0.125 g) and IPDI (120.8 g). The reaction was heated to 50°C. Then 0.1 g of bismuth neodecanoate was added. After the exotherm was complete, the reaction was maintained at 90°C for 150 minutes. The NCO content of the resulting isocyanate-terminated prepolymer was 2.29% (theoretically 2.45%). The prepolymer was cooled to 80°C, TEA (18.8 g) was added, and mixed at 80°C for 10 minutes.
[0293] A dispersion of the obtained isocyanate-terminated prepolymer was prepared by adding 286 g of the obtained prepolymer mixture to deionized water (580 g) under nitrogen atmosphere over 45 minutes. The dispersion temperature was controlled between 25-30° C. and hydrazine (13.6 g) was added after the addition was complete.
[0294] Subsequently, tBHPO (2.8 g (10% aqueous solution)) and Fe(II)EDTA (0.28 g (1% aqueous solution)) were added to the dispersion, followed by isoascorbic acid (16.7 g (1% aqueous solution)) (pH>7), which was added slowly over 15 minutes. The resulting polyurethane-vinyl polymer hybrid dispersion had a solids content of 30.9 wt% solids and a pH of 7.8. The specifications of the resulting polyurethane-vinyl polymer hybrid are listed in Table 2.
[0295] Preparation of polyurethane-vinyl polymer hybrid resin dispersion (UA Ex.9)
[0296] A dispersion of the isocyanate terminated prepolymer in UA Ex.8 was prepared by adding 178 g of the resulting prepolymer mixture to deionized water (450 g) over 45 minutes under a nitrogen atmosphere. The dispersion temperature was controlled between 25 and 30°C. Hydrazine (8.5 g) was added after the feeds were completed. Subsequently, MMA (71.6 g) and BA (32.6 g) were added to the polyurethane dispersion and mixed for 45 minutes. Thereafter, tBHPO (6.9 g (10% aqueous solution)) and Fe(II)EDTA (0.7 g (1% aqueous solution)) were added to the dispersion, followed by isoascorbic acid (42 g (1% aqueous solution)) (pH>7), which was added slowly over 15 minutes. The resulting polyurethane-vinyl polymer hybrid dispersion had a solids content of 35.7 wt% solids and a pH of 7.8. The specifications of the resulting polyurethane-vinyl polymer hybrid are shown in Table 2.
[0297] Preparation of polyurethane-vinyl polymer hybrid resin dispersion (UA Ex.10)
[0298] A 2000 cm 3 The flask was charged with components pTHF2000 (229.5 g), DMPA (16.6 g), BHT (0.08 g), MMA (83.5 g), DesW (73.5 g) and HDI (13.0 g). The reaction was heated to 50°C and 0.07 g of bismuth neodecanoate was added. After the exotherm was complete, the reaction was maintained at 90°C for 150 minutes. The NCO content of the resulting isocyanate-terminated prepolymer was 2.36%. After cooling to 80°C, TEA (12.6 g) was added and mixed for 15 minutes.
[0299] A dispersion of the resulting isocyanate-terminated prepolymer was prepared by adding 286 g of the resulting prepolymer mixture to deionized water (808 g) under a nitrogen atmosphere over 45 minutes. The dispersion temperature was controlled between 25 and 30° C. After the addition was complete, hydrazine (16% aqueous solution, 14.0 g) was added.
[0300] Subsequently, 0.4 g of 10% tBHPO solution and 0.28 g of 1% Fe(II)EDTA solution were added. Finally, 17 g of 1% isoascorbic acid solution (pH>7) were added to the dispersion over 10 minutes. The specifications of the resulting polyurethane-vinyl polymer hybrid are listed in Table 2.
[0301] Preparation of polyurethane-vinyl polymer hybrid resin dispersion (UA CEx.1)
[0302] A 2000 cm 3 The flask was charged with components pTHF650 (110.2 g), NPG (13.0 g), DMPA (16.2 g), BHT (0.08 g), MMA (83.6 g) and IPDI (184.7 g). The reaction was heated to 50°C and 0.07 g of bismuth neodecanoate was added. After the exotherm was complete, the reaction was maintained at 90°C for 150 minutes. The NCO content of the resulting isocyanate-terminated prepolymer was 8.35%. After cooling to 80°C, TEA (12.2 g) was added and mixed for 15 minutes.
[0303] A dispersion of the resulting isocyanate-terminated prepolymer was prepared by adding 280 g of the resulting prepolymer mixture to deionized water (453 g) over 45 minutes under a nitrogen atmosphere. The dispersion temperature was controlled between 25 and 30° C. After the addition was complete, hydrazine (16% aqueous solution, 48.6 g) was added.
[0304] Subsequently, 0.4 g of 10% tBHPO solution and 0.28 g of 1% Fe(II)EDTA solution were added. Finally, 17 g of 1% isoascorbic acid solution (pH>7) were added to the dispersion over 10 minutes. The specifications of the resulting polyurethane-vinyl polymer hybrid are listed in Table 2.
[0305] Table 2: Specifications for UA Ex.1 to 12 and comparative experiment UA CEx.1
[0306]
[0307]
[0308] Table 2 continued
[0309] UAEx.8 UAEx.9 UAEx.10 UAEx.11 UAEx.12 UACEx.1 U / A ratio 80 / 20 50 / 50 80 / 20 80 / 20 60 / 40 80 / 20 Acid value of mixture (A) [mgKOH / g(A)] <![CDATA[ 16 .6]]> <![CDATA[ 10 .3]]> <![CDATA[ 16 .5]]> <![CDATA[ 19 .9]]> <![CDATA[ 14 .9]]> <![CDATA[ 16 .1]]> Tg of vinyl polymer phase [℃] 105 50 105 50 0 105 Urea content in polyurethane [meq / gPU] 0.69 0.69 0.67 0.74 0.74 2.35 Solid content [wt%] 30.9 35.7 25.5 34.8 34.8 36.2 Mn[kg / mole] 19.6 30.7 30.7 75.1 89.1 32.4 Mw[kg / mole] 236 708 589 1378 1806 512 pH 7.6 7.3 8.1 7.9 7.8 7.4 PS[nm] 86 103 146 52 84 87
[0310] Preparation of formulations
[0311] The polyurethane vinyl polymer hybrid dispersions of Examples 1-12 and Comparative Experiment 1 were formulated as shown in Table 3. The ingredients listed in Table 3 were added to a PE jar and (Orange Line, ATP Engineering BV) and mix thoroughly.
[0312] Table 3 : Preparation of UV-curable polyurethane-vinyl polymer hybrid resin formulations (FUA Ex.1a-FUA Ex.15a and FUACEx.1-FUA CEx.3)
[0313]
[0314] Table 3 continued
[0315]
[0316]
[0317] For litter formulations FUA Ex1b-15b, 1.8 g of Acematt TS-100 was added to 100 g of formulations FUA Ex. 1-15, respectively, see Table 4.
[0318] Table 4: Matting agent containing formulations FUA 1b-FUA15b
[0319] Formulations containing matting agents FUAEx.1b-15b Formulations FUAEx.1a-15a 100g AcemattTS-100 1.8g
[0320] Application of formulation
[0321] The coating composition thus obtained was applied to a Leneta card (2C Leneta Inc) using a 125 μm wire rod applicator. The coated card was dried in an oven at 50° C. at an air velocity of 1.2 m / s for 10 minutes. The dried composition thus obtained was then cured, and the curing conditions are shown in Tables 5-7. In Table 8, 125, 75, 50 and 25 μm wire rod applicators were used, respectively.
[0322] Curing of the dried coating composition
[0323] Excimer / UV curing:
[0324] Immediately after drying (within 20 seconds), the formulation was cured on a UVio curing rig equipped with 2 lamps at a conveyor speed of 15 m / min. The first lamp was an Excirad 172 lamp (IOT GmbH, a xenon-based excimer lamp generating 172 nm light), under which a 11.4 mJ / cm 2The next curing step was performed with a second lamp, which was a Light Hammer 10 Mark III (Heraeus Holding, Hg-doped UV lamp) equipped with an H-bulb operating at 50% power, generating UV light with a wavelength of ≥315 nm, with a total dose of 181 mJ / cm2 as measured with a Power Puck II (EIT Inc). 2 ).
[0325] Conventional UV atmospheric curing (Conv UVcure atmosph):
[0326] Immediately after drying (within 20 seconds), the formulation was cured on a UVio curing unit with a conveyor speed of 15 m / min. The total dose was 181 mJ / cm2 as measured with a Power Puck II (EIT Inc) by a Light Hammer 10 Mark III (Heraeus Holding, Hg-doped UV lamp) equipped with an H-bulb operating at 50% power. 2 ) The curing step is carried out in air.
[0327] Conventional UV inert atmosphere curing (Conv UVcure inert):
[0328] Immediately after drying (within 20 seconds), the formulation was cured on a UVio curing unit with a conveyor speed of 15 m / min. The total dose was 181 mJ / cm2 as measured with a Power Puck II (EIT Inc) by a Light Hammer 10 Mark III (Heraeus Holding, Hg-doped UV lamp) equipped with an H-bulb operating at 50% power. 2 ) The curing step is carried out under an inert atmosphere.
[0329] Testing of Cured Coatings
[0330] The gloss and coffee, red wine and mustard resistance of the cured coatings were determined as described above. The measured gloss values are reported in Tables 5 and 7. The coffee, red wine and mustard resistance are reported in Tables 5 and 6.
[0331] Table 5: measured gloss values of formulations without matting agent and cured with excimer / UV curing; gloss values of formulations with matting agent and cured with conventional UV curing under atmospheric conditions; colorimetrically measured stain resistance of formulations without matting agent and cured with excimer / UV curing, and colorimetrically measured stain resistance of formulations with matting agent and cured with conventional UV curing under atmospheric conditions (Conv UV atmosph) and conventional UV curing under inert conditions (Conv UVinert), respectively
[0332]
[0333] Figure 1 Shown are coated test cards obtained by the excimer / UV curing method according to the process of the present invention for formulation 5a containing the polyurethane vinyl polymer hybrid dispersion of Example 5 but without a matting agent (upper test card) and coated test cards obtained by conventional UV curing under atmospheric conditions for formulation 5b containing the polyurethane vinyl polymer hybrid dispersion of Example 5 and a matting agent (bottom test card);
[0334] From left to right: coffee [6 hours], red wine [6 hours], mustard [6 hours], and coffee [1 hour] stains.
[0335] Table 6 : Colorimetric stain resistance of formulations without matting agent and cured with excimer / UV curing (Δb for coffee and mustard and Δa for red wine)
[0336]
[0337] Table 7 : Gloss values measured for formulations without matting agent after combined excimer / UV curing and conventional UV curing under atmospheric conditions
[0338]
[0339]
[0340] Table 8: Effect of layer thickness on gloss
[0341]
[0342] With the process of the present invention, low gloss coatings can be obtained at very low dry thicknesses, even low gloss coatings with a dry thickness of 4 microns can be obtained, whereas when the formulation contains a matting agent (formulation FUA Ex. 4b) and the formulation is cured with conventional UV curing, no suitable film with such a low dry thickness can be obtained.
[0343] Comparative Experiment 4-10
[0344] A representative set of commercially available waterborne UV-curable coating dispersions as specified in Table 9 were applied to Leneta cards (2C Leneta Inc) using a 125 μm wire bar applicator. The coated cards were dried in an oven at 50° C. at an air velocity of 1.2 m / s for 10 minutes. The dried composition thus obtained was subsequently cured using conventional UV atmospheric curing and excimer / UV curing as described above. The measured gloss values are reported in Table 9. The commercially available waterborne UV-curable coating compositions as shown in Table 9 have different compositions from the waterborne radiation-curable coating compositions of the present invention.
[0345] Table 9 : Gloss values of a representative set of commercially available waterborne UV-curable coating compositions after conventional UV curing and combined excimer / UV curing under atmospheric conditions
[0346]
[0347] Table 9 shows that this representative set of commercially available waterborne UV-curable dispersions did not give a matte coating when subjected to excimer / UV curing.
Claims
1. A method for producing a coating from an aqueous radiation-curable coating composition, wherein the method comprises the following steps in the order (1) to (4): (1) applying an aqueous radiation-curable coating composition onto a surface of a substrate, (2) drying the aqueous radiation-curable coating composition to provide an at least partially dried coating composition, (3) irradiating the at least partially dried coating composition with ultraviolet light having a wavelength of ≤220 nm under an inert atmosphere, and then (4) Irradiation with ultraviolet light with a wavelength of ≥300nm or electron beam, The aqueous radiation-curable coating composition is a dispersion comprising: (A) at least one blend (A) of at least one polyurethane and at least one vinyl polymer, wherein The hybrid (A) is obtained by free radical polymerization of at least one vinyl monomer in the presence of at least one water-dispersible polyurethane, The hybrid (A) contains substantially no radiation-curable ethylenically unsaturated bonds, The polyurethane of the hybrid (A) has a urea group (—NH—CO—NH—) concentration of at least 0.1 milliequivalent / gram of polyurethane and at most 1.9 milliequivalent / gram of polyurethane, and The weight ratio of the polyurethane and the vinyl polymer of the blend (A) is 25:75 to 95:5; (B) at least one radiation-curable diluent (B) having a molar mass of less than 750 g / mol and having an acrylate functionality of 2 to 5, and (C) water and optionally an organic solvent, whereby the optional organic solvent is present in an amount of up to 30% by weight, based on the total amount of water and organic solvent, in The amount of (A) is 30 to 85% by weight, and the amount of (B) is 15 to 70% by weight, based on the total amount of (A) and (B).
2. The process according to claim 1, wherein the polyurethane of the hybrid (A) has a urea group content of at most 1.7 meq / g polyurethane, more preferably at most 1.5 meq / g polyurethane, more preferably at most 1.3 meq / g polyurethane, more preferably at most 1.1 meq / g polyurethane, more preferably at most 0.9 meq / g polyurethane, and preferably at least 0.2 meq / g polyurethane, more preferably at least 0.3 meq / g polyurethane, even more preferably at least 0.35 meq / g polyurethane.
3. A process according to any one of the preceding claims, wherein the polyurethane and the vinyl polymer are present in the polyurethane-vinyl polymer blend (A) in a weight ratio of 30:70 to 90:10, more preferably 40:60 to 88:12, more preferably 50:50 to 85:15, more preferably 65:35 to 80:
20.
4. A method according to any one of the preceding claims, - wherein the polyurethane-vinyl polymer blend (A) has an acid value of 3 to 45 mg KOH / g blend (A), preferably 4 to 40 mg KOH / g blend (A), more preferably 5 to 35 mg KOH / g blend (A), more preferably 6 to 28 mg KOH / g blend (A); and / or wherein the polyurethane of the polyurethane-vinyl polymer hybrid (A) has an acid value of 5 to 50, more preferably 10 to 40, even more preferably 15 to 30 mg KOH / g polyurethane solids; and / or - wherein the vinyl polymer of blend (A) has an acid value of 0 to 10 mg KOH / g vinyl polymer solids, preferably less than 8 mg KOH / g vinyl polymer solids, more preferably less than 5 mg KOH / g vinyl polymer solids, more preferably less than 3 mg KOH / g vinyl polymer solids; and / or - wherein the glass transition temperature T of the vinyl polymer of the blend (A) g It is -55°C to 115°C, preferably -20°C to 115°C, more preferably -5°C to 115°C. 5 . The process according to claim 1 , wherein the at least one radiation curable diluent (B) has an acrylate functionality of 2 to 4.
6. The process according to any one of claims 1 to 5, wherein at least 10 wt. %, preferably at least 20 wt. %, more preferably at least 30 wt. %, more preferably at least 40 wt. %, more preferably at least 50 wt. %, more preferably at least 60 wt. %, more preferably at least 70 wt. %, more preferably at least 80 wt. %, more preferably at least 90 wt. %, and most preferably 100 wt. % of the radiation curable diluent (B) is selected from: With the corresponding molecular formula C 24 H 34 O9 and its corresponding di(trimethylolpropane)tetraacrylate (di-TMPTA) with a molar mass of 467 g / mol, Di(trimethylolpropane)tetraacrylate containing an alkoxy group, With the corresponding molecular formula C 21 H 32 O8 and its corresponding di(trimethylolpropane) triacrylate (di-TMP3A) with a molar mass of 412 g / mol, di(trimethylolpropane) triacrylate containing an alkoxy group, With the corresponding molecular formula C 21 H 32 O9 and its corresponding glyceryl propoxy triacrylate (GPTA) with a molar mass of 428 g / mol, Glyceryl propoxy triacrylate containing an additional alkoxy group, With the corresponding molecular formula C 17 H 20 O8 and its corresponding pentaerythritol tetraacrylate (PET4A) with a molar mass of 352 g / mol, Pentaerythritol tetraacrylate containing an alkoxy group, With the corresponding molecular formula C 14 H 18 O7 and its corresponding pentaerythritol triacrylate (PET3A) with a molar mass of 298 g / mol, Pentaerythritol triacrylate containing an alkoxy group, With the corresponding molecular formula C 15 H 20 O6 and its corresponding trimethylolpropane triacrylate (TMPTA) with a molar mass of 296 g / mol, trimethylolpropane triacrylate containing an alkoxy group, With the corresponding molecular formula C 12 H 18 O5 and its corresponding dipropylene glycol diacrylate (DPGDA) with a molar mass of 242 g / mol, Dipropylene glycol diacrylate containing an additional alkoxy group, and any mixture thereof.
7. A method according to any one of the preceding claims, in - based on the total amount of (A) and (B), the amount of (A) is 35 to 80% by weight, and the amount of (B) is 20 to 65% by weight, more preferably, the amount of (A) is 40 to 80% by weight, and the amount of (B) is 20 to 60% by weight; and / or - the total amount of (A) and (B) is preferably 10 to 60 wt %, more preferably 15 to 50 wt %, more preferably 15 to 45 wt %, even more preferably 20 to 40 wt %, even more preferably 25 to 35 wt %, based on the total weight of the aqueous radiation curable coating composition; and / or - the amount of water in the aqueous radiation curable coating composition is at least 30 wt%, or at least 35 wt%, or at least 40 wt%, or at least 45 wt%, or at least 50 wt%, or at least 55 wt%, or at least 60 wt%, or at least 70 wt%, based on the total weight of the aqueous radiation curable coating composition; and / or - the optional organic solvent is present in an amount of up to 25 wt.-%, preferably in an amount of up to 20 wt.-%, preferably in an amount of up to 15 wt.-%, preferably in an amount of up to 10 wt.-%, more preferably in an amount of up to 5 wt.-%, more preferably in an amount of up to 4 wt.-%, more preferably in an amount of up to 3 wt.-%, more preferably in an amount of up to 2 wt.-%, more preferably in an amount of up to 1 wt.-%, wherein the amount of organic solvent is given based on the total amount of water and organic solvent present in the aqueous radiation curable coating composition.
8. The method according to any one of the preceding claims, wherein the polyurethane is the reaction product of at least the following components: (A1) at least one polyisocyanate, (A2) at least one isocyanate-reactive compound containing at least one salt group capable of rendering the polyurethane dispersible in water and / or at least one functional group convertible into a salt group capable of rendering the polyurethane dispersible in water, (A3) optionally, at least one isocyanate-reactive compound containing at least one nonionic group capable of rendering the polyurethane dispersible in water, (A4) at least one isocyanate-reactive polyol different from (A2) and (A3) having an OH number of 25 to 225 mg KOH / g solids, (A5) optionally, at least one isocyanate-reactive polyol different from (A2) and (A3) having an OH value of more than 225 mg KOH / g solid and less than 1850 mg KOH / g solid, and (A6) water and / or at least one nitrogen-containing chain extender compound; wherein the isocyanate-reactive polyol (A4) preferably has an OH value of 35 to 190 mg KOH / g solid, more preferably 45 to 125 mg KOH / g solid, and the polyurethane comprises the isocyanate-reactive polyol (A4) in an amount of preferably 20 to 80% by weight, more preferably 30 to 70% by weight, even more preferably 35 to 65% by weight, based on the weight of the polyurethane; and / or The polyurethane preferably comprises at least one NH x (wherein x is 1 or 2) a nitrogen-containing chain extender having a functionality of 9. A method according to any one of the preceding claims, wherein the hybrid (A) has a radiation-curable ethylenically unsaturated bond concentration of less than 0.20 milliequivalents (meq) / gram of hybrid (A), more preferably less than 0.10 meq / g of hybrid (A), more preferably less than 0.05 meq / g of hybrid (A), even more preferably less than 0.01 meq / g of hybrid (A), wherein the radiation-curable ethylenically unsaturated bond concentration is determined by the method as described in the specification; and / or wherein (A) and (B) together have a radiation-curable ethylenic unsaturation concentration of 0.8 to 5.0 milliequivalents (meq) / gram (A)+(B), preferably 1.5 to 4 milliequivalents (meq) / gram (A)+(B), wherein the radiation-curable ethylenic unsaturation concentration is determined by the method as described in the specification.
10. The method according to any one of the preceding claims, wherein the dispersion consisting of (A), (B) and (C) has a z-average particle size of 20 to 1000 nm, preferably 25 to 500 nm, more preferably 25 to 250 nm, and most preferably 30 to 200 nm, whereby the z-average particle size is determined by the method as described in the description.
11. A method according to any preceding claim, wherein the coating has a dry thickness of at least 2 microns, or at least 3 microns, or at least 4 microns, and at most 100 microns, or at most 75 microns, or at most 50 microns.
12. The method according to any one of the preceding claims, wherein the irradiation in step (3) is carried out by an excimer UV lamp, preferably with UV light having a wavelength ≥120 nm, more preferably ≥150 nm, and particularly preferably 172 nm or 195 nm.
13. The method according to any one of the preceding claims, wherein UV radiation is applied in step (4) and the aqueous radiation curable coating composition comprises one or more photoinitiators.
14. An aqueous radiation curable coating composition as defined in any one of claims 1 to 10.
15. A coated substrate, wherein the coated substrate is obtained by the method according to any one of claims 1 to 13.
Citation Information
Patent Citations
Acylphosphine oxide compounds
US4324744A
Bisacylphosphine oxides, the preparation and use thereof
US4737593A
Daylight curing compositions containing bisacylphosphine oxide photoinitiators
US5534559A
Molecular complex compounds of acylphosphine oxide and alpha -hydroxy ketones as photoinitiators
US5942290A
Alkylphenylbisacylphosphine oxides and photoinitiator mixtures
US6020528A